Adhesive tape for workpiece processing

By using the adhesive tape between the polyester film substrate and a specific acrylate monomer copolymer intermediate layer, the problem of uneven thickness and separation of residual glue in the treatment of semiconductor and glass substrates in the prior art is solved, and the bonding effect of high precision and high flexibility is achieved, ensuring the integrity and quality of the treatment process.

JP7626647B2Active Publication Date: 2025-02-04MAXELL LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021060722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-04
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

The prior art is difficult to provide an adhesive tape that can satisfy both high thickness accuracy and high flexibility during back grinding and cutting, especially when dealing with semiconductor wafers and glass substrates, to avoid wafer damage or fragmentation caused by uneven thickness of the adhesive tape, and to avoid the problem of adhesive tape being disengaged from the annular frame or retaining glue during cutting.

Method used

An adhesive tape consisting of a polyester film base material and an intermediate layer is used, which consists of acrylate monomer copolymers with a specific proportion. Combined with a reactive hardened adhesive layer, ensuring that good adhesion can be maintained before and after active radiation, and weakening the adhesion through reactive radiation for peeling after cutting or back grinding is completed.

Benefits of technology

In the processing of semiconductor wafers and glass substrates, the adhesive tape can maintain strong adhesive force before and after the active performance radiation, avoiding the adhesive tape from being separated from the annular frame or retaining glue, ensuring high-quality completion of the cutting and back grinding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626647000022
    Figure 0007626647000022
  • Figure 0007626647000023
    Figure 0007626647000023
  • Figure 0007626647000024
    Figure 0007626647000024
Patent Text Reader

Abstract

To provide an adhesive tape for workpiece processing which is usable as a backgrinding tape capable of coping with grinding and ultra-thinning of a semiconductor wafer, and is also usable as a dicing tape.SOLUTION: An adhesive tape for workpiece processing includes a polyester-based resin base material film, an intermediate layer, and an active energy ray-curable adhesive layer in this order, wherein the intermediate layer is formed from a resin composition containing a ternary or more (meth)acrylate copolymer (A1) containing methyl acrylate and a methacrylic acid, the total amount of a copolymer monomer component constituting (A1) is 100 pts.mass, 47 to 67 pts.mass of methyl acrylate and 2 to 7 pts.mass of a methacrylic acid are contained, and the active energy ray-curable adhesive layer contains a (meth)acrylate copolymer (A2) in which a photosensitive carbon-carbon double bond is introduced to a side chain of the (meth)acrylate copolymer base polymer containing n-butyl acrylate as a main component of the copolymer monomer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape for work processing that can be suitably used when processing workpieces such as semiconductor wafers and glass substrates. [Background technology]

[0002] Conventionally, as a process for manufacturing a semiconductor chip of a semiconductor device, a back grinding process (hereinafter, sometimes simply referred to as "grinding") for thinning a semiconductor wafer by grinding a semiconductor wafer having a circuit formed on its surface to a predetermined thickness from its back side with a grinding wheel, and a dicing process (hereinafter, sometimes simply referred to as "cutting" or "cutting") for dividing a semiconductor wafer into individual semiconductor chips are known. In addition, as a process for manufacturing, for example, a camera module for a smartphone or a medical sensor, a dicing process for dividing a glass substrate into individual glass chips is known. As an adhesive tape used when processing such a workpiece as a semiconductor wafer or a glass plate, for example, a back grinding tape or a dicing tape having an active energy ray curable adhesive layer on a base film can be mentioned.

[0003] The backgrind tape is used to stably hold and fix the semiconductor wafer and protect the circuit surface in the backgrind process. The specific method of use is as follows. First, the backgrind tape is attached to the surface of the semiconductor wafer on which the circuits are formed to fix the semiconductor wafer, and the backside of the semiconductor wafer is ground to a specified thickness with a grinding wheel while spraying water on it. After the grinding process is completed, the adhesive layer of the backgrind tape is irradiated with active energy rays such as ultraviolet (UV) rays to reduce the adhesive force, and the backgrind tape is peeled off from the semiconductor wafer.

[0004] The dicing tape is used to fix the thinned semiconductor wafer so as not to shift position and to prevent the diced semiconductor chips from scattering when the semiconductor wafer, which has been thinned by grinding in the back grinding process, is cut to a predetermined size by, for example, a rotating dicing blade and diced into individual semiconductor chips. A specific method of use is as follows. First, the dicing tape is attached to a ring frame, and then the thinned semiconductor wafer is attached and placed on the adhesive layer. Next, cutting is performed so that the semiconductor wafer is diced into individual chips of a predetermined size while supplying running water toward the dicing blade and the semiconductor wafer for the purpose of removing cutting waste that is inevitably generated. After the cutting process is completed, the adhesive layer of the dicing tape is irradiated with active energy rays such as ultraviolet (UV) rays to reduce the adhesive force, and the diced semiconductor chips are picked up from the adhesive layer by a pick-up device. Before picking up, the dicing tape is expanded as necessary. After picking up is completed, the dicing tape is manually peeled off from the ring frame. The ring frame from which the dicing tape has been peeled off is washed and reused.

[0005] In recent years, with the thinning of semiconductor devices, there is a demand for grinding semiconductor wafers even thinner in the backgrinding process. In order to grind semiconductor wafers to a thickness thinner than before, a backgrinding tape with higher thickness accuracy than before is required. That is, if the thickness of the backgrinding tape is non-uniform, the non-uniformity affects the semiconductor wafer, causing the thickness of the semiconductor wafer after grinding to be non-uniform, or in the worst case, the semiconductor wafer may be damaged. In order to improve the thickness accuracy of the backgrinding tape, it is considered preferable to use a polyester film such as a polyethylene terephthalate film with high thickness accuracy as the base film (Patent Document 1).

[0006] Also, in the above dicing process, unlike the case of semiconductor wafers, in order to dice a workpiece that is brittle and easily breakable, such as a glass substrate, or a hard workpiece, such as a sapphire glass or quartz substrate, a dicing tape that is less deformed during dicing than conventional dicing tapes is required. That is, if the deformation of the dicing tape during dicing is large, the glass substrate cannot withstand the deformation and breaks, causing chipping (chipping of the edge or cut surface of the glass chip) or chip flying, which may cause quality problems for the cut glass substrate pieces. In addition, when dicing a hard sapphire glass substrate, the chips may be misaligned, causing chipping due to collision between chips, chip pick-up errors, or poor dimensional accuracy of the chips. In order to suppress deformation of the dicing tape, it is considered preferable to use a polyester film, such as a polyethylene terephthalate film, which has a large tensile modulus and is relatively hard, as the base film (Patent Document 2).

[0007] Meanwhile, from the viewpoint of users who use the above-mentioned adhesive tape for processing workpieces, there is a demand to avoid increasing the number of types of adhesive tape for processing workpieces as much as possible, for example, to avoid incorrect input of adhesive tape used in each process, or to improve production efficiency. That is, there is a demand for an adhesive tape for processing workpieces that can be used as a backgrind tape that can handle grinding and ultra-thinning of semiconductor wafers, and can also be used as a dicing tape that can handle cutting of fragile workpieces such as glass substrates. Also, from the viewpoint of manufacturers who manufacture adhesive tape for processing workpieces, an adhesive tape having such functions is desired to improve production efficiency. However, it is highly difficult to simultaneously satisfy the characteristics required in each process for the reasons described below, and it has been difficult to achieve.

[0008] In order to realize such a workpiece processing adhesive tape that can be used in both the backgrinding process for extremely thinning semiconductor wafers and the dicing process for brittle and easily broken glass substrates, it is preferable to use at least a polyester film such as a polyethylene terephthalate film as the base film, as described above. However, when an active energy ray curable adhesive layer is directly laminated on a polyester film to form a backgrinding tape or dicing tape, the adhesion between the base film and the active energy ray curable adhesive layer may be insufficient compared to conventional backgrinding tapes or dicing tapes using relatively flexible and extensible base films such as polyolefin films. That is, the active energy ray curable adhesive layer has the characteristic that it is three-dimensionally polymerized and cured by irradiation with active energy rays, and causes volume shrinkage from the normal state before curing, and the elastic modulus also increases. And, by utilizing this phenomenon, a workpiece such as a semiconductor wafer or a glass chip can be easily peeled off from the adhesive layer. However, since the relatively flexible and extensible polyolefin film can follow the volumetric shrinkage of the adhesive layer to some extent, the adhesion between the active energy ray curable adhesive and the polyolefin film is maintained, but since the polyester film has a high surface smoothness and is rigid, it is difficult to follow the volumetric shrinkage of the adhesive layer, so the adhesion between the active energy ray curable adhesive layer and the polyester film may decrease. As a result, for example, when peeling from the semiconductor wafer, the active energy ray curable adhesive may peel off from the polyester film at the interface, and the energy ray curable adhesive may transfer to the surface of the semiconductor wafer.

[0009] Patent Document 1 discloses an adhesive sheet in which a polyester substrate film, an anchor coat layer containing a compound having an energy ray-polymerizable group, and an energy ray-curable adhesive layer are laminated in this order, for the purpose of providing an adhesive sheet in which the energy ray-curable adhesive layer is not transferred to a wafer or the like, even when a polyester film is used as the substrate of the energy ray-curable adhesive sheet. It is presumed that when the energy ray-curable adhesive is cured, at least a part of the energy ray-polymerizable group contained in the anchor coat layer is also polymerized, forming a covalent bond between a part of the adhesive layer and the anchor coat layer, and the adhesive layer and the substrate can maintain adhesion via the anchor coat layer.

[0010] The adhesive sheet described in Patent Document 1 is specifically an adhesive sheet for protecting the circuit surface of a semiconductor wafer when grinding the back surface of the semiconductor wafer. It is said that this adhesive sheet can also be used to temporarily fix a wafer in a dicing process of a semiconductor wafer, but when this adhesive sheet is used as a dicing tape for a glass substrate or a sapphire glass substrate, the following problems may occur. Usually, the dicing tape is subjected to the dicing process in a state where it is attached to a ring frame. In the dicing process, cleaning water is sprayed to cool the frictional heat generated between the dicing blade rotating at high speed and the glass substrate or the sapphire glass substrate and to remove the cutting chips, but the dicing tape needs to be firmly attached to the ring frame so as to withstand the load and water pressure. In addition, the dicing tape may be expanded as necessary, so even in that case, the dicing tape needs to be firmly attached so as not to peel off from the ring frame. In the case of a dicing tape having an active energy ray curable adhesive layer, the adhesive strength of the part irradiated with active energy rays is reduced, so the adhesive layer of the part attached to the ring frame (glue part) is usually not irradiated with active energy rays to maintain high adhesive strength. In this case, when the adhesive sheet described in Patent Document 1 is attached to a ring frame and subjected to a dicing process without irradiating the gluing part with active energy rays, the adhesive strength of the interface between the anchor coat layer and the energy ray curable adhesive layer may be insufficient, and there is a risk that the adhesive sheet may peel off from the ring frame during the dicing process, or that the adhesive layer may transfer (remain glue) to the ring frame when the dicing tape that is no longer needed is peeled off from the ring frame after the required process. As a result, the number of washings to remove the adhesive from the ring frame increases, and at the same time, the life of the ring frame may be shortened. In addition, such a problem is not described.

[0011] Patent Document 2 discloses an adhesive sheet for dicing glass substrates, which provides cut pieces with excellent shape and is less susceptible to chipping or chip flying, and has an adhesive layer with a thickness of 9 μm or less provided on a base film with a thickness of 130 μm or more and a tensile elastic modulus of 1 GPa or more. In the examples, an ultraviolet-curable adhesive sheet is exemplified, in which an ultraviolet-curable adhesive layer is formed on a polyester film (tensile elastic modulus 1.5 GPa) having one side subjected to a corona treatment, as the base film.

[0012] The adhesive sheet of Patent Document 2 is an adhesive sheet for dicing glass substrates, but there is no description of adhesive residue on the ring frame. As described above, when the dicing tape that is no longer needed is peeled off from the ring frame after the dicing process, it is unclear whether the adhesive layer will transfer (residual adhesive) to the ring frame, and there is a concern that adhesive will remain. In addition, when the adhesive sheet of Patent Document 2 is used as a backgrind tape for a semiconductor wafer, the following problems may occur. That is, when the backgrind tape is peeled off after the required process, the surface has unevenness due to the circuit formation, and it is peeled off from the entire surface of the semiconductor wafer with a large area, so the load on the interface between the base film and the ultraviolet-curable adhesive layer is large, and there is a concern that the ultraviolet-curable adhesive layer will peel off from the interface from the base film, and the ultraviolet-curable adhesive will transfer to the surface of the semiconductor wafer. Furthermore, the adhesive sheet of Patent Document 2 has a relatively thin thickness, which makes it difficult to follow the circuits formed on the surface of the semiconductor wafer, and cannot provide sufficient protection, so there is a risk that grinding water will penetrate into the interface between the semiconductor wafer and the adhesive layer during grinding. Furthermore, when exposed to active energy rays after grinding, the tape is susceptible to oxygen inhibition, and the ultraviolet-curable adhesive layer does not cure sufficiently, which may result in adhesive residue remaining on the peripheral edge of the circuit surface when the unnecessary backgrind tape is peeled off from the entire surface of the semiconductor wafer.

[0013] As described above, in order to realize an adhesive tape for work processing that can be used as a backgrind tape capable of grinding and ultra-thinning semiconductor wafers, and that can also be used as a dicing tape capable of cutting fragile workpieces such as glass substrates and hard workpieces such as sapphire glass substrates, it is necessary to ensure sufficient adhesion between the polyester film base film and the active energy ray-curable adhesive layer at least both before and after irradiation with active energy rays, but such an adhesive tape for work processing has not yet been found. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2013-23665 A [Patent Document 2] JP 2004-10829 A Summary of the Invention [Problem to be solved by the invention]

[0015] The present invention has been made in consideration of the above problems and circumstances, and aims to provide a work processing adhesive tape in which, when a polyester film is used as a base film and an active energy ray curable adhesive layer is used as an adhesive layer, the adhesion between the base film and the active energy ray curable adhesive is sufficiently large both before and after irradiation with active energy rays, and even when used as a backgrind tape for extremely thinning a semiconductor wafer, the active energy ray curable adhesive layer can be peeled off without being transferred to the semiconductor wafer during peeling, and even when used as a dicing tape for cutting a brittle work such as a glass substrate or a hard work such as a sapphire glass substrate, the tape does not peel off from the ring frame during the process and can be peeled off without leaving any adhesive residue when peeled off from the ring frame. That is, the objective is to provide a work processing adhesive tape that can be used as a backgrind tape that can handle grinding and extremely thinning of semiconductor wafers, and can also be used as a dicing tape that can handle cutting a brittle work such as a glass substrate or a hard work such as a sapphire glass substrate. [Means for solving the problem]

[0016] That is, the adhesive tape for workpiece processing of the present invention comprises a base film made of a polyester resin composition, an intermediate layer, and an active energy ray-curable adhesive layer in this order, the intermediate layer is made of a resin composition containing a ternary or higher (meth)acrylic acid ester copolymer (A1) containing methyl acrylate (MA) and methacrylic acid (MAA) as copolymer monomer components; the methyl acrylate (MA) is contained in an amount of from 47 parts by mass to 67 parts by mass, and the methacrylic acid (MAA) is contained in an amount of from 2 parts by mass to 7 parts by mass, based on 100 parts by mass of the total amount of copolymer monomer components constituting the ternary or higher (meth)acrylic acid ester copolymer (A1); The active energy ray-curable pressure-sensitive adhesive layer is made of a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced into a side chain of a binary or more (meth)acrylic acid ester copolymer base polymer (BP) and a crosslinking agent; The binary or higher (meth)acrylic acid ester copolymer base polymer (BP) contains n-butyl acrylate (n-BA) as a copolymer monomer component in a proportion of more than 50 parts by mass and not more than 90 parts by mass, based on 100 parts by mass of the total amount of copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer (BP). It is characterized by:

[0017] In one embodiment, the ternary or higher (meth)acrylic acid ester copolymer (A1) is a ternary or higher (meth)acrylic acid ester copolymer containing 2-ethylhexyl acrylate (2-EHA) as a copolymer monomer component other than the methyl acrylate (MA) and methacrylic acid (MAA).

[0018] In one embodiment, the ternary or higher (meth)acrylic acid ester copolymer (A1) is a ternary (meth)acrylic acid ester copolymer having 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA) as copolymer monomer components, and when the total amount of the copolymer monomer components constituting the ternary (meth)acrylic acid ester copolymer is taken as 100 parts by mass as a reference, the 2-ethylhexyl acrylate (2-EHA) is contained in a range of 26 parts by mass or more and 51 parts by mass or less, the methyl acrylate (MA) is contained in a range of 47 parts by mass or more and 67 parts by mass or less, and the methacrylic acid (MAA) is contained in a range of 2 parts by mass or more and 7 parts by mass or less, so that the total amount of the copolymer monomer components is 100 parts by mass.

[0019] In one embodiment, the ternary or higher (meth)acrylic acid ester copolymer (A1) has a glass transition temperature (Tg) in the range of -36°C or higher and -9°C or lower.

[0020] In one embodiment, the binary or higher (meth)acrylic acid ester copolymer base polymer (BP) is a ternary (meth)acrylic acid ester copolymer having n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA) as copolymer monomer components, and contains the n-butyl acrylate (n-BA) in the range of 66 parts by mass to 90 parts by mass, the 2-hydroxyethyl acrylate (2-HEA) in the range of 9.8 parts by mass to 31 parts by mass, and the methacrylic acid (MAA) in the range of 0.2 parts by mass to 3 parts by mass, so that the total amount of the copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer (BP) is 100 parts by mass.

[0021] In one embodiment, the binary or higher (meth)acrylic acid ester copolymer base polymer (BP) has a glass transition temperature (Tg) in the range of -50°C or higher and -39°C or lower.

[0022] In one embodiment, the intermediate layer has a thickness of 5 μm or more.

[0023] In one embodiment, the active energy ray-curable pressure-sensitive adhesive layer has a thickness of 5 μm or more.

[0024] In one embodiment, the sum of the thickness of the intermediate layer and the thickness of the active energy ray-curable pressure-sensitive adhesive layer is 10 μm or more.

[0025] In one embodiment, the substrate film made of the polyester resin composition is a polyethylene terephthalate film.

[0026] In one embodiment, the adhesive strength of the adhesive tape for work processing to a glass plate before exposure to ultraviolet rays is in the range of 5.0 N / 25 mm or more and 25.0 N / 25 mm or less, and the adhesive strength after exposure to ultraviolet rays is in the range of 0.01 N / 25 mm or more and 0.50 N / 25 mm or less.

[0027] In one embodiment, the adhesive strength of the adhesive tape for work processing to a stainless steel plate (SUS304BA plate) before ultraviolet irradiation is in the range of 5.0 N / 25 mm or more and 25.0 N / 25 mm or less, and the adhesive strength after ultraviolet irradiation is in the range of 0.01 N / 25 mm or more and 0.50 N / 25 mm or less. Effect of the Invention

[0028] According to the present invention, when a film made of a polyester resin composition is used as the base film and an active energy ray curable adhesive layer is used as the adhesive layer, the adhesion between the base film and the active energy ray curable adhesive is sufficiently large both before and after irradiation with active energy rays, and even when used as a backgrind tape for extremely thinning a semiconductor wafer, the active energy ray curable adhesive layer can be peeled off without being transferred to the semiconductor wafer during peeling, and even when used as a dicing tape for cutting a brittle work such as a glass substrate or a hard work such as a sapphire glass substrate, the adhesive tape does not peel off from the ring frame during the process and can be peeled off without leaving any adhesive residue when peeled off from the ring frame. That is, it is possible to provide an adhesive tape for work processing that can be used as a backgrind tape that can handle grinding and extremely thinning of semiconductor wafers, and can also be used as a dicing tape that can handle cutting a brittle work such as a glass substrate. [Brief description of the drawings]

[0029] [Figure 1] 1 is a cross-sectional view showing an example of the configuration of an adhesive tape for workpiece processing to which the present embodiment is applied. [Diagram 2] 10 is a cross-sectional view showing an example of another embodiment of the configuration of the adhesive tape for workpiece processing to which the present embodiment is applied. FIG. [Diagram 3] This is an oblique view showing from above a ring frame (wafer ring) attached to the outer edge of an adhesive tape for workpiece processing to which this embodiment is applied, and a glass substrate that has been individualized by a dicing process adhered and held in the center of the adhesive tape for workpiece processing. [Figure 4] 1 is a schematic cross-sectional view showing an embodiment of the adhesive tape for work processing, which is used in a dicing process. FIG. [Diagram 5] 1 is a perspective view showing a state in which an adhesive tape for workpiece processing to which the present embodiment is applied is being peeled off from a ring frame, as viewed from below. FIG. [Figure 6] 1A and 1B are schematic cross-sectional views showing an embodiment in which an adhesive tape for workpiece processing to which this embodiment is applied is used in a back-grinding process: (a) before grinding; (b) after thinning. [Figure 7] 1A to 1C are schematic diagrams showing a process of peeling an adhesive tape for work processing, to which an embodiment is applied, from a thinned semiconductor wafer surface, starting from a peeling tape: (a) a cross-sectional view before peeling; (b) an oblique view from above showing the state during peeling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings as necessary. However, the present invention is not limited to the following embodiments.

[0031] <Composition of adhesive tape for workpiece processing> FIG. 1 is a cross-sectional view showing an example of the structure of the adhesive tape for workpiece processing to which the present embodiment is applied. As shown in FIG. 1, the adhesive tape for workpiece processing 10 has a structure in which an intermediate layer 2 and an active energy ray curable adhesive layer 3 are provided in this order on one side of a base film 1. Although not shown, a base sheet (release liner) having releasability may be provided on the surface of the active energy ray curable adhesive layer 3 of the adhesive tape for workpiece processing 10 (the surface opposite to the surface facing the base film 1). The base film 1 is composed of a polyester-based resin composition. The intermediate layer 2 is formed from a resin composition containing a predetermined (meth)acrylic acid ester copolymer. The active energy ray curable adhesive layer 3 is formed from an adhesive composition containing a (meth)acrylic acid ester copolymer in which a photosensitive carbon-carbon double bond is introduced into the side chain of a predetermined (meth)acrylic acid ester copolymer base polymer (BP).

[0032] Fig. 2 is a cross-sectional view showing an example of another embodiment of the structure of the adhesive tape for workpiece processing to which the present embodiment is applied. As shown in Fig. 2, the adhesive tape for workpiece processing 10 has a structure in which an intermediate layer 2 and an active energy ray curable adhesive layer 3 are provided in this order on one side of a base film 1, but while the base film 1 in Fig. 1 has a single layer structure, the base film 1 in Fig. 2 has a laminated structure of a resin layer 1a made of a polyester resin composition and a resin layer 1b made of a resin composition containing a resin other than polyester, for example. The other structures are the same as those in Fig. 1.

[0033] The adhesive tape 10 for workpiece processing having such a configuration is used in a dicing process in which a hard workpiece, such as a brittle and easily broken glass substrate on which various circuit formations or surface treatments have been performed, a quartz substrate, or a sapphire glass substrate, is cut and separated into small pieces. It can also be used in a dicing process for a normal silicon semiconductor wafer or a compound semiconductor wafer such as silicon carbide, gallium arsenide, gallium phosphide, or gallium nitride. That is, it is used as a dicing tape, specifically, as shown in FIG. 3 and FIG. 4. First, a ring frame 20 made of SUS is attached to the active energy ray curable adhesive layer 3 at the outer edge of the adhesive tape 10 for workpiece processing, which has been punched into a circle, and then, for example, a glass substrate 30 is attached to the active energy ray curable adhesive layer 3 at the center of the adhesive tape 10 for workpiece processing so that the surface side on which no circuit formation has been performed is in contact with the active energy ray curable adhesive layer 3. Here, the thickness of the workpiece, such as a glass substrate, a quartz substrate, or a sapphire glass substrate, is, for example, in the range of 50 μm to 5000 μm. Next, the glass substrate 30 is cut into glass chips 30a of a predetermined size by a dicing blade 40 rotating at high speed while spraying cleaning and cooling water. Here, the planar area of ​​the chip is, for example, 1×10 -6 mm 2 ~9mm 2 After cutting, active energy rays such as ultraviolet light (UV) are irradiated from the base film 1 side of the adhesive tape 10 for workpiece processing to the portion of the active energy ray curable adhesive layer 3 to which the workpiece is attached, thereby reducing the adhesive strength of the active energy ray curable adhesive layer 3, and the glass chip 30a is picked up (peeled off) from the active energy ray curable adhesive layer 3 of the adhesive tape 10 for workpiece processing. This makes it possible to obtain high-quality glass chips 30a in which chipping is suppressed.

[0034] 5 is a perspective view showing a state in which the adhesive tape 10 for workpiece processing, which is no longer necessary, is peeled off from the ring frame 20 after picking up all the glass chips 30a has been completed. The adhesive tape for workpiece processing is peeled off from the ring frame by hand, but it may also be peeled off using a peeling device or the like. The ring frame 20 from which the adhesive tape for workpiece processing 10 has been peeled off is washed and reused as necessary. However, if the adhesive layer of the active energy ray curable adhesive layer peels off from the base film 1 and transfers (leaves adhesive residue) to the surface of the ring frame 10 when the adhesive tape for workpiece processing 10 is peeled off, it takes time to clean it, and the work efficiency decreases.

[0035] The adhesive tape 10 for workpiece processing having such a configuration can also be used in a backgrinding process for grinding semiconductor wafers such as silicon wafers on which various circuits have been formed or other surface treatments have been applied, to an extremely thin thickness. That is, it is used as a backgrinding tape, specifically, as shown in FIG. 6. First, as shown in FIG. 6(a), the active energy ray curable adhesive layer 3 side of the adhesive tape 10 for workpiece processing is bonded to the surface side on which the circuit 51 of the semiconductor wafer 50 having a thickness of, for example, 775 μm is formed. Next, the semiconductor wafer 50 is ground from the surface opposite to the surface on which the circuit has been formed, by a grinder (grinding wheel) 60, while supplying grinding water, until the semiconductor wafer 50 reaches a predetermined thickness. At this time, the semiconductor wafer 50 is adsorbed and held on a holding table (not shown) via the adhesive tape 10 for workpiece processing. FIG. 6(b) shows a state in which the grinding of the semiconductor wafer 50 is completed and the semiconductor wafer 50' in a state of being thinned to a predetermined thickness is held by the adhesive tape 10 for workpiece processing. Here, the thickness of the semiconductor wafer 50' in a thinned state is, for example, in the range of 20 μm or more and 100 μm or less.

[0036] After grinding, first, active energy rays such as ultraviolet light (UV) are irradiated from the base film 1 side of the workpiece processing adhesive tape 10 to the active energy ray curable adhesive layer 3 portion to which the thinned semiconductor wafer 50' is attached, thereby curing the active energy ray curable adhesive layer 3 and reducing the adhesive force. Next, as shown in FIG. 7(a), a SUS ring frame 20 is attached to the active energy ray curable adhesive layer 3 at the outer edge of a separately prepared circular punched dicing tape 11, and then the grinding surface side of the thinned semiconductor wafer 50' is attached to the active energy ray curable adhesive layer 3 at the center of the dicing tape 11 so that it contacts the active energy ray curable adhesive layer 3. Next, a strip-shaped (e.g., 50 mm wide x 60 mm long) peeling tape 12 is attached to the back surface of the base film 1 of the workpiece processing adhesive tape 10 by pressure bonding or thermocompression bonding. The adhesive tape 10 for workpiece processing has substantially the same shape as the thinned semiconductor wafer 50', and since there is no starting point for peeling, the strip-shaped peeling tape 12 is firmly fixed to serve as the starting point for peeling. Then, before the next dicing process, as shown in FIG. 7(b), the adhesive tape 10 for workpiece processing is peeled from the surface of the thinned semiconductor wafer 50' having the circuit 51 on its surface, starting from the peeling tape 12. The peeling is performed manually or by using a peeling device or the like. At this time, the thinned semiconductor wafer 50' is held by suction on a holding table (not shown) via the dicing tape 11. This makes it possible to obtain a thinned semiconductor wafer 50' with high thickness accuracy without any contamination such as glue residue on the surface.

[0037] <Adhesive tape for workpiece processing> (Base film) The base film 1 in the adhesive tape 10 for workpiece processing according to the present embodiment will be described below. As the base film 1, a film made of a polyester resin composition is used from the viewpoint of tensile strength and rigidity. The film made of the polyester resin composition is a film mainly composed of polyester, and the polyester is preferably contained in a proportion of 70% by mass or more relative to the total resin components (components of the resin composition excluding additives other than resin) in the resin composition constituting the base film 1, and more preferably contained in a proportion of 80% by mass or more, which is close to the composition of polyester alone. There is no particular limit to the upper limit, and it is 100% by mass or less.

[0038] Examples of polyesters that are the main component of the base film 1 include crystalline linear saturated polyesters obtained by polycondensation of aromatic dibasic acids or their ester derivatives with diols or their ester derivatives. Specific examples of polyesters include homopolyesters such as polyethylene terephthalate, polyethylene isophthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalenedicarboxylate, and copolymer polyesters that mainly contain these resin components. The polyesters can also be used by blending the homopolyesters together, or the homopolyesters and the copolymer polyesters. Among these polyesters, polyethylene terephthalate is particularly preferred because it is easy to obtain, has good mechanical strength (tensile strength, rigidity, etc.), transparency, and heat resistance, and is easy to obtain a base film 1 with high thickness accuracy.

[0039] Examples of the aromatic dibasic acid of the homopolyester include terephthalic acid, 2,6-naphthalenedicarboxylic acid, etc., and examples of the diol include ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, etc. The repeating units of the homopolyester, i.e., the total of the main repeating units consisting of the aromatic dibasic acid constituents and the diol constituents, is preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more of the total repeating units.

[0040] Examples of the aromatic dibasic acid of the copolymer polyester include oxycarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and paraoxybenzoic acid, and these can be used alone or in combination of two or more kinds.

[0041] Examples of the diol in the copolymer polyester include ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol, which can be used alone or in combination of two or more kinds.

[0042] The mass ratio of the copolymerization component of the copolymer polyester is preferably less than 20% by mass, whereby the mechanical strength, transparency, heat resistance, and thickness accuracy of the base film 1 can be maintained.

[0043] The polyester is preferably contained in an amount of 70% by mass or more relative to the total resin components constituting the base film 1 (components obtained by excluding additives other than resins from the resin composition), but the resin components may contain other resins other than the polyester, such as aromatic ether compounds, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, polyolefin elastomers, polyamide elastomers, polycarbonate resins, ionomer resins, etc., as necessary. From the viewpoint of maintaining the mechanical strength, transparency, heat resistance, and thickness accuracy of the base film 1, the other resins are preferably contained in an amount of 30% by mass or less, and more preferably 20% by mass or less, relative to the total resin components constituting the base film 1 (components obtained by excluding additives other than resins from the resin composition).

[0044] As another embodiment of the polyester, which is the main component of the base film 1, there may be mentioned a so-called polyester-polyether block type thermoplastic elastomer, in which an aromatic polyester is used for the hard segment and a polyether is used for the soft segment, or a so-called polyester-polyester block type thermoplastic elastomer, in which an aromatic polyester is used for the hard segment and an aliphatic polyester is used for the soft segment. Specifically, the polyester-polyether block type thermoplastic elastomer may be a thermoplastic polyester elastomer in which polybutylene terephthalate is used for the polyester in the hard segment and polytetramethylene ether glycol is used for the polyether in the soft segment, and the polyester-polyester block type thermoplastic elastomer may be a thermoplastic polyester elastomer in which polybutylene terephthalate is used for the polyester in the hard segment and polylactone is used for the polyester in the soft segment.

[0045] The polyester resin composition constituting the base film 1 preferably contains particles for the main purpose of imparting easy slippage to the base film 1. The type of particles to be added is not particularly limited as long as it is a particle capable of imparting easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and heat-resistant organic particles such as thermosetting urea resin, thermosetting phenolic resin, thermosetting epoxy resin, and benzoguanamine resin. The shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, and the like may be used. Two or more types of these series of particles may be used in combination as necessary.

[0046] The length-average particle diameter of the particles is usually in the range of 0.01 μm to 3 μm, preferably 0.01 μm to 1 μm. When the average particle diameter is within the above range, appropriate slipperiness and smoothness can be imparted to the base film 1. The content of the particles is usually in the range of 0.001 mass % to 5 mass %, preferably 0.005 mass % to 3 mass %, based on the total resin components constituting the base film 1. When the content of the particles is within the above range, appropriate slipperiness and smoothness can be imparted.

[0047] In addition, in addition to the above-mentioned particles, the polyester resin composition may contain conventionally known catalysts, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc., as necessary, within the scope of not impairing the effects of the present invention.

[0048] As the base film 1 made of the polyester resin composition, any of a non-stretched polyester film, a uniaxially stretched polyester film, and a biaxially stretched polyester film can be used, but a biaxially stretched polyester film is preferred. Specifically, a biaxially stretched polyethylene terephthalate film is preferred.

[0049] The base film 1 may have a single layer structure or a laminate structure of two or more layers. From the viewpoint of process simplification and thickness accuracy, the base film 1 is preferably a single layer structure as shown in FIG. 1. When the base film 1 has a two-layer structure, it has a laminate structure of a resin layer 1a composed of a polyester resin composition and a resin layer 1b composed of a resin composition other than polyester, for example, as shown in FIG. 2. Here, the resin layer 1a is a layer on the side directly contacting the intermediate layer 2, and when the base film 1 has a laminate structure, at least the resin layer 1a directly contacting the intermediate layer 2 is composed of the polyester resin composition. The resin layer 1b may be a layer composed of a resin composition other than polyester, or may be a layer composed of a polyester resin composition. In addition, as the resin component of the resin composition other than polyester, the same resin as the resin exemplified as the other resin other than polyester described above can be used.

[0050] The total thickness of the base film 1 is not particularly limited as long as it can be formed into a film, but is usually in the range of 12 μm to 250 μm, preferably 25 μm to 188 μm, and more preferably 38 μm to 125 μm. If the total thickness of the base film 1 is less than 12 μm, the handleability during the manufacture of the adhesive tape for work processing 10 or during use in the process may be poor, and as a result, the quality of the processed work (glass chip 30a, thinned semiconductor wafer 50', etc.) may be poor. On the other hand, if the total thickness exceeds 250 μm, the rigidity may be too high, and as a result, the quality of the processed work may be poor.

[0051] When the base film 1 has a laminated structure of two or more layers, the total thickness of the layers composed of the polyester resin composition cannot be generally determined because it depends on the total thickness of the entire base film 1, but it is preferable to set the thickness to a ratio of 50% or more to the total thickness of the entire base film 1. When the ratio is 50%, the quality of the processed workpiece is good.

[0052] (Middle class) The intermediate layer 2 in the adhesive tape 10 for workpiece processing according to this embodiment will be described below. The intermediate layer 2 is made of a resin composition containing a ternary or more (meth)acrylic acid ester copolymer (A1) (hereinafter, sometimes simply referred to as "(meth)acrylic acid ester copolymer (A1)") containing methyl acrylate (MA) and methacrylic acid (MAA) as copolymer monomer components, and contains at least the methyl acrylate (MA) in a range of 47 parts by mass to 67 parts by mass and the methacrylic acid (MAA) in a range of 2 parts by mass to 7 parts by mass, when the total amount of the copolymer monomer components constituting the ternary or more (meth)acrylic acid ester copolymer (A1) is taken as 100 parts by mass as a reference. ester Copolymer (A 1 The content of the component (a) in the total amount of the resin composition is preferably 90% by mass or more, and more preferably 95% by mass or more.

[0053] [(Meth)acrylic acid ester copolymer (A1)] In the ternary or higher (meth)acrylic acid ester copolymer (A1), by containing methyl acrylate (MA) and methacrylic acid (MAA) as copolymer monomer components in the above-mentioned ranges, the adhesion between the above-mentioned base film 1 and the intermediate layer 2, and the adhesion between the intermediate layer 2 and the active energy ray-curable adhesive layer 3 described below can both be improved, and even after the adhesive tape for work processing 10 is irradiated with active energy rays, the adhesion can be sufficiently maintained at a level that does not interfere with work processing. As a result, the quality of the processed work can be improved.

[0054] The ternary or higher (meth)acrylic acid ester copolymer (A1) contains copolymer monomer components other than the methyl acrylate (MA) and methacrylic acid (MAA) in an amount of 26 parts by mass or more and 51 parts by mass or less, based on 100 parts by mass of the total amount of copolymer monomer components constituting the (meth)acrylic acid ester copolymer (A1).

[0055] The copolymer monomer components other than the above methyl acrylate (MA) and methacrylic acid (MAA) are not particularly limited as long as they are monomers capable of copolymerization with the above methyl acrylate (MA) and methacrylic acid (MAA), and examples thereof include (meth)acrylic acid ester monomers having a linear or branched alkyl group having from 2 to 20 carbon atoms, (meth)acrylic acid cycloalkyl ester monomers, functional group-containing monomers, vinyl acetate, styrene, acrylonitrile, N-methylvinylpyrrolidone, etc. These monomers can be used alone or in combination of two or more kinds.

[0056] Specific examples of the (meth)acrylic acid ester monomer having a linear or branched alkyl group having 2 to 20 carbon atoms include ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, from the viewpoints of versatility, adhesion between the intermediate layer 2 and the active energy ray-curable adhesive layer 3, and adhesion between the intermediate layer 2 and the base film 1, a (meth)acrylic acid ester monomer having a linear or branched alkyl group having from 2 to 8 carbon atoms is preferred, and specifically, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. are preferably used.

[0057] Specific examples of the (meth)acrylic acid cycloalkyl ester monomer include cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.

[0058] Specific examples of the functional group-containing monomer include carboxyl group-containing monomers such as acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itaconic anhydride; hydroxy group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate; Examples of the monomers include sulfonic acid group-containing monomers such as benzenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; glycidyl group-containing monomers such as (meth)acrylic acid glycidyl ester; amide group-containing monomers such as (meth)acrylic acid amide and (meth)acrylic acid N-hydroxymethylamide; and amino group-containing monomers such as (meth)acrylic acid alkylamino alkyl esters such as (meth)acrylic acid dimethylaminoethyl and (meth)acrylic acid t-butylaminoethyl. Among these, from the viewpoints of versatility, adhesion between the intermediate layer 2 and the active energy ray curable pressure-sensitive adhesive layer 3, adhesion between the intermediate layer 2 and the base film 1, and improvement of the cohesive force of the intermediate layer 2, acrylic acid, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and (meth)acrylic acid amide are preferably used.

[0059] As the ternary or higher (meth)acrylic acid ester copolymer (A1) in the present invention, it is preferable to use a ternary or higher (meth)acrylic acid ester copolymer containing 2-ethylhexyl acrylate (2-EHA) as a copolymer monomer component in addition to the above-mentioned specific copolymer monomer components of methyl acrylate (MA) and methacrylic acid (MAA). Specific examples of such ternary or higher (meth)acrylic acid ester copolymers include: (1) Terpolymer of 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA); (2) a quaternary copolymer of 2-ethylhexyl acrylate (2-EHA), n-butyl acrylate (n-BA), methyl acrylate (MA), and methacrylic acid (MAA); (3) quaternary copolymer of 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA); (4) quaternary copolymer of 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), ethyl acrylate (EA), and methacrylic acid (MAA); (5) A quaternary copolymer of 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), acrylic acid (AA), and methacrylic acid (MAA) etc.

[0060] Among these, from the viewpoint of versatility, a ternary (meth)acrylic acid ester copolymer having 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA) as copolymer monomer components, or a ternary copolymer of n-butyl acrylate (n-BA), methyl acrylate (MA), and methacrylic acid (MAA) can be preferably used, and a ternary (meth)acrylic acid ester copolymer having 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA) as copolymer monomer components can be more preferably used.

[0061] When a ternary (meth)acrylic acid ester copolymer of 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA) is used as the ternary or higher (meth)acrylic acid ester copolymer (A1), it is preferable that the respective monomer components are adjusted so that, when the total amount of the copolymer monomer components constituting the ternary (meth)acrylic acid ester copolymer is taken as 100 parts by mass, the total amount of the copolymer monomer components is 100 parts by mass, with 2-ethylhexyl acrylate (2-EHA) in the range of 26 parts by mass to 51 parts by mass, methyl acrylate (MA) in the range of 47 parts by mass to 67 parts by mass, and methacrylic acid (MAA) in the range of 2 parts by mass to 7 parts by mass.

[0062] The ternary or higher (meth)acrylic acid ester copolymer (A1) is obtained by subjecting a mixture of the methyl acrylate (MA) monomer, the methacrylic acid (MAA) monomer, and one or more monomers selected from the above-mentioned monomers other than these two monomers, which are blended in a predetermined amount as copolymer monomer components, to polymerization. The polymerization can be carried out by any method such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, etc. The weight average molecular weight (Mw) of the ternary or higher (meth)acrylic acid ester copolymer (A1) is preferably 100,000 or more from the viewpoint of improving the cohesive force of the intermediate layer 2, and is preferably 1.5 million or less from the viewpoint of the suitability of applying the solution of the resin composition of the intermediate layer 2. That is, the weight average molecular weight (Mw) is preferably in the range of 100,000 to 1.5 million, and more preferably in the range of 300,000 to 1 million. Here, the weight average molecular weight (Mw) is the weight average molecular weight in terms of standard polystyrene measured using gel permeation chromatography (GPC).

[0063] The glass transition temperature (Tg) of the ternary or higher (meth)acrylic acid ester copolymer (A1) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but from the viewpoints of adhesion between the above-mentioned base film 1 and the intermediate layer 2, adhesion between the intermediate layer 2 and the active energy ray-curable adhesive layer 3 described below, and processing quality of the work, it is preferably in the range of -36°C or higher to -9°C or lower, and more preferably in the range of -36°C or higher to -18°C or lower. Here, the glass transition temperature (Tg) is a theoretical value calculated from the Fox formula shown in the following general formula (1) based on the composition of the monomer components constituting the ternary or higher (meth)acrylic acid ester copolymer (A1).

[0064]

number

[0065] The glass transition temperatures (Tg) of homopolymers can be found, for example, in "Polymer Handbook," edited by J. Brandrup and EH Immergut, Interscience Publishers.

[0066] If the glass transition temperature (Tg) is within the above range, for example, when a brittle and easily broken workpiece such as a glass substrate 30 is diced by a rotating dicing blade 40, the workpiece on the adhesive layer 3 is well held and fixed, and furthermore, the shaking can be suppressed, so that chipping and dimensional deviation and positional deviation of the chip can be suppressed. In addition, when the adhesive tape 10 for workpiece processing is peeled off from the ring frame 20 after dicing, the adhesive layer can be suppressed from leaving adhesive residue on the ring frame 20 and from transferring the adhesive layer. In addition, for example, when grinding the semiconductor wafer 50, the adhesive tape 10 for workpiece processing can appropriately follow the steps of the circuits 51 and electrodes on the surface of the semiconductor wafer 50, so that the adhesive layer 10 for workpiece processing can be suppressed from leaving adhesive residue on the periphery of the circuit surface when peeled off from the thinned semiconductor wafer 50' and the uniformity of the thickness of the thinned semiconductor wafer 50' can be ensured. In addition, the adhesive layer 3 can also be suppressed from transferring to the thinned semiconductor wafer 50'.

[0067] Further, the acid value of the ternary or higher (meth)acrylic acid ester copolymer (A1) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but from the viewpoints of adhesion between the above-mentioned base film 1 and the above-mentioned intermediate layer 2, adhesion between the above-mentioned intermediate layer 2 and the active energy ray curable adhesive layer 3 described later, and improving the cohesive force of the intermediate layer 2, it is preferably 13.0 mgKOH / g or more, and from the viewpoints of suppressing gelation during polymerization of the copolymer (A1) and the rigidity of the intermediate layer 2 (reduction in adhesive strength before active energy ray irradiation of the adhesive tape for work processing 10 and reduction in step followability due to increased rigidity), it is preferably 50.7 mgKOH / g or less. That is, the acid value is preferably in the range of 13.0 mgKOH / g or more and 50.7 mgKOH / g or less.

[0068] Furthermore, the hydroxyl value of the ternary or higher (meth)acrylic acid ester copolymer (A1) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but from the viewpoints of adhesion between the above-mentioned base film 1 and the intermediate layer 2, adhesion between the intermediate layer 2 and the active energy ray-curable adhesive layer 3 described below, and the rigidity of the intermediate layer 2 (a decrease in the adhesive strength of the adhesive tape for work processing 10 before exposure to active energy rays and a decrease in its ability to conform to unevenness due to increased rigidity), it is preferably in the range of 0 mgKOH / g or more and 96.6 mgKOH / g or less.

[0069] [Crosslinking agent] In order to improve the cohesive strength of the intermediate layer 2, the resin composition constituting the intermediate layer 2 preferably contains a crosslinking agent capable of reacting with the functional group of the ternary or higher (meth)acrylic acid ester copolymer (A1). Such a crosslinking agent is not particularly limited, and a known crosslinking agent having a functional group capable of reacting with the functional group of the ternary or higher (meth)acrylic acid ester copolymer (A1), i.e., a carboxyl group, or a hydroxyl group, glycidyl group, etc., introduced as necessary, can be used. Specific examples of the crosslinking agent include polyisocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, aziridine-based crosslinking agents, melamine resin-based crosslinking agents, urea resin-based crosslinking agents, acid anhydride compound-based crosslinking agents, polyamine-based crosslinking agents, and carboxyl group-containing polymer-based crosslinking agents. Among these, it is preferable to use a polyisocyanate-based crosslinking agent or an epoxy-based crosslinking agent from the viewpoint of reactivity and versatility. These crosslinking agents may be used alone or in combination of two or more. The amount of the crosslinking agent is preferably in the range of 0.01 parts by mass or more and 10.0 parts by mass or less, and more preferably in the range of 0.1 parts by mass or more and 5.0 parts by mass or less, relative to 100 parts by mass of the solid content of the ternary or higher (meth)acrylic acid ester copolymer (A1).

[0070] Examples of the polyisocyanate crosslinking agent include a polyisocyanate compound having an isocyanurate ring, an adduct polyisocyanate compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, an adduct polyisocyanate compound obtained by reacting trimethylolpropane with tolylene diisocyanate, an adduct polyisocyanate compound obtained by reacting trimethylolpropane with xylylene diisocyanate, an adduct polyisocyanate compound obtained by reacting trimethylolpropane with isophorone diisocyanate, etc. These may be used alone or in combination of two or more.

[0071] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, etc. These can be used alone or in combination of two or more.

[0072] Thickness The thickness of the intermediate layer 2 may be adjusted appropriately depending on the processing of the work, but is not particularly limited as long as it is within a range that does not impede the effects of the present invention, and is preferably, for example, 5 μm or more from the viewpoint of adhesion between the above-mentioned base film 1 and the intermediate layer 2 and adhesion between the intermediate layer 2 and the active energy ray-curable pressure-sensitive adhesive layer 3 described below, and is preferably 150 μm or less from the viewpoint of proper application and drying of the solution of the resin composition of the intermediate layer 2. That is, the thickness of the intermediate layer 2 is preferably in the range of 5 μm or more and 150 μm or less, and more preferably in the range of 5 μm or more and 100 μm or less.

[0073] (Active energy ray curable adhesive layer) The active energy ray curable adhesive layer 3 (hereinafter, sometimes simply referred to as "adhesive layer 3") in the adhesive tape 10 for workpiece processing of this embodiment will be described below. The active energy ray curable adhesive layer 3 is made of an adhesive composition containing a (meth)acrylic acid ester copolymer (A2) (hereinafter, sometimes simply referred to as "(meth)acrylic acid ester copolymer (A2)") in which a photosensitive carbon-carbon double bond has been introduced into the side chain of a binary or more (meth)acrylic acid ester copolymer base polymer (BP), and a crosslinking agent. The content ratio of the (meth)acrylic acid ester copolymer (A2) to the total amount of the adhesive composition is preferably 90% by mass or more, and more preferably 95% by mass or more.

[0074] The method for producing the (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced into the side chain is not particularly limited, but typically includes a method in which a copolymer monomer component containing a (meth)acrylic acid ester monomer and a functional group-containing monomer is copolymerized to obtain a (meth)acrylic acid ester copolymer base polymer, and then a compound having a functional group capable of undergoing an addition reaction with the functional group possessed by the base polymer and a carbon-carbon double bond (active energy ray reactive compound) is subjected to an addition reaction.

[0075] [(Meth)acrylic acid ester copolymer base polymer (BP)] The binary or higher (meth)acrylic acid ester copolymer base polymer (BP) (hereinafter, may be simply referred to as base polymer (BP)) in this embodiment contains n-butyl acrylate (n-BA) as a copolymer monomer component in an amount of more than 50 parts by mass and not more than 90 parts by mass, assuming that the total amount of copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer (BP) is 100 parts by mass as a reference.

[0076] In the above-mentioned binary or more (meth)acrylic acid ester copolymer base polymer (BP), as described above, by containing n-butyl acrylate (n-BA) as a copolymer monomer component in a ratio of more than 50 parts by mass and not more than 90 parts by mass when the total amount of the copolymer monomer components constituting the base polymer (BP) is taken as 100 parts by mass as a standard, the adhesion between the above-mentioned intermediate layer 2 and the above-mentioned adhesive layer 3 can be improved, and the adhesion can be sufficiently maintained at a level that does not interfere with the processing of the workpiece both before and after the irradiation of the active energy ray of the adhesive tape 10 for workpiece processing. On the other hand, it is possible to impart a high adhesive strength of the adhesive tape 10 for workpiece processing before the irradiation of the active energy ray, which is necessary for holding the workpiece during processing of the workpiece, and a cohesive strength of the adhesive layer 3, which is necessary for suppressing adhesive residue on the workpiece when the adhesive tape 10 for workpiece processing is peeled off from the processed workpiece. As a result, the quality of the processed workpiece can be improved.

[0077] In addition, when the total amount of the copolymer monomer components constituting the base polymer (BP) is taken as 100 parts by mass as the standard, the binary or higher (meth)acrylic acid ester copolymer base polymer (BP) preferably contains, as copolymer monomer components other than the n-butyl acrylate (n-BA), a functional group-containing monomer in an amount of 10 parts by mass or more and 34 parts by mass or less, and other copolymer monomers (excluding n-BA and functional group-containing monomers) in an amount of 0 parts by mass or more and less than 40 parts by mass, adjusted so that the total amount of the copolymer monomer components is 100 parts by mass.

[0078] Examples of the functional group-containing monomer include the same carboxyl group-containing monomer, acid anhydride monomer, hydroxyl group-containing monomer, sulfonic acid group-containing monomer, glycidyl group-containing monomer, amide group-containing monomer, and amino group-containing monomer as those exemplified above as the functional group-containing monomer component of the ternary or higher (meth)acrylic acid ester copolymer (A1) of the intermediate layer 2. These can be used alone or in combination of two or more. Among these, it is preferable to use a hydroxyl group-containing monomer from the viewpoint of ease of addition reaction with the active energy ray reactive compound described later. Specific examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, from the viewpoint of versatility, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred.

[0079] The purpose of copolymerizing the functional group-containing monomer is, first, to make the functional group into an addition reaction site for introducing an active energy ray-reactive carbon-carbon double bond described later into the binary or more (meth)acrylic acid ester copolymer base polymer (BP) by an addition reaction; second, to make the functional group into a crosslinking reaction site for polymerizing the (meth)acrylic acid ester copolymer (A2) by reacting with a crosslinking agent described later; third, to make an active site (polar site) for improving the initial adhesion between the active energy ray-curable pressure-sensitive adhesive layer 3 and the workpiece after the crosslinking reaction; and fourth, to make an active site (polar site) for improving the adhesion between the intermediate layer 2 and the active energy ray-curable pressure-sensitive adhesive layer 3. As described above, the content ratio of the functional group-containing monomer is preferably adjusted in the range of 10% by mass or more and 34% by mass or less with respect to the total amount of copolymer monomer components constituting the binary or more (meth)acrylic acid ester copolymer base polymer (BP).

[0080] In addition, the binary or higher (meth)acrylic acid copolymer base polymer (BP) may contain other copolymer monomers (excluding n-BA and functional group-containing monomers) as copolymer monomer components in a proportion of less than 40% by mass based on the total amount of copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer (BP) from the viewpoints of improving cohesive strength, adjusting glass transition temperature (Tg), improving heat resistance, etc., as necessary. The other copolymer monomer components are not particularly limited as long as they are monomers capable of copolymerization with the n-butyl acrylate (n-BA) and the functional group-containing monomers, and examples thereof include (meth)acrylic acid ester monomers having a linear or branched alkyl group with a carbon number of 1 to 20, (meth)acrylic acid cycloalkyl ester monomers, vinyl acetate, styrene, acrylonitrile, and N-methylvinylpyrrolidone. These monomers may be used alone or in combination of two or more.

[0081] Specific examples of the (meth)acrylic acid ester monomer having a linear or branched alkyl group having from 1 to 20 carbon atoms include methyl (meth)acrylate having a linear alkyl group having one carbon atom, as well as the same as those exemplified above as the copolymer monomer components of the ternary or higher (meth)acrylic acid ester copolymer (A1) of the intermediate layer 2, that is, (meth)acrylic acid ester monomers having a linear or branched alkyl group having from 2 to 20 carbon atoms. Among these, from the viewpoint of versatility, methyl (meth)acrylate, ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, etc. are preferred.

[0082] Specific examples of the (meth)acrylic acid cycloalkyl ester monomer include cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.

[0083] In the present embodiment, it is preferable to use a binary or higher (meth)acrylic acid ester copolymer containing n-butyl acrylate (n-BA) and 2-hydroxyethyl acrylate (2-HEA) as copolymer monomer components as the binary or higher (meth)acrylic acid ester copolymer base polymer (BP). Specific examples of such binary or higher (meth)acrylic acid ester copolymers include: (1) A copolymer of n-butyl acrylate (n-BA) and 2-hydroxyethyl acrylate (2-HEA); (2) terpolymer of n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA); (3) quaternary copolymer of n-butyl acrylate (n-BA), 2-ethylhexyl acrylate (2-EHA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA); (4) A quaternary copolymer of n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), methyl methacrylate (MMA), and methacrylic acid (MAA) etc.

[0084] Among these, from the viewpoint of versatility, a binary (meth)acrylic acid ester copolymer having n-butyl acrylate (n-BA) and 2-hydroxyethyl acrylate (2-HEA) as copolymer monomer components, or a ternary (meth)acrylic acid ester copolymer having n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA) as copolymer monomer components can be preferably used, and a ternary (meth)acrylic acid ester copolymer having n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA) as copolymer monomer components can be more preferably used.

[0085] When a binary (meth)acrylic acid ester copolymer of n-butyl acrylate (n-BA) and 2-hydroxyethyl acrylate (2-HEA) is used as the binary or higher (meth)acrylic acid ester copolymer base polymer (BP), it is preferable that the respective monomer components are adjusted so that, when the total amount of the copolymer monomer components constituting the ternary (meth)acrylic acid ester copolymer is taken as 100 parts by mass, the total amount of the copolymer monomer components is 100 parts by mass, with n-butyl acrylate (n-BA) in the range of 66 parts by mass or more and 90 parts by mass or less, and 2-hydroxyethyl acrylate (2-HEA) in the range of 10 parts by mass or more and 34 parts by mass or less.

[0086] When a ternary (meth)acrylic acid ester copolymer of n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA) is used as the binary or higher (meth)acrylic acid ester copolymer base polymer (BP), it is preferable that the respective monomer components are adjusted so that the total amount of the copolymer monomer components constituting the ternary (meth)acrylic acid ester copolymer is 100 parts by mass, with n-butyl acrylate (n-BA) in the range of 66 parts by mass to 90 parts by mass, 2-hydroxyethyl acrylate (2-HEA) in the range of 9.8 parts by mass to 31 parts by mass, and methacrylic acid (MAA) in the range of 0.2 parts by mass to 3 parts by mass.

[0087] The glass transition temperature (Tg) of the binary or more (meth)acrylic acid ester copolymer base polymer (BP) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but is preferably in the range of -50°C or more and -39°C or less from the viewpoints of adhesion between the intermediate layer 2 and the active energy ray curable adhesive layer 3, adhesive strength control of the adhesive tape for work processing before and after irradiation with active energy rays, and processing quality of the work. Here, the glass transition temperature (Tg) is a theoretical value calculated from the Fox formula based on the composition of the monomer components constituting the binary or more (meth)acrylic acid ester copolymer base polymer (BP).

[0088] If the glass transition temperature (Tg) is within the above range, for example, when a brittle and easily broken workpiece such as a glass substrate 30 is diced by a rotating dicing blade 40, the workpiece on the adhesive layer 3 can be firmly fixed, so that chip positional deviation and chip flying can be suppressed. In addition, since the adhesion between the intermediate layer 2 and the adhesive layer 3 described above is improved, it is possible to suppress adhesive residue on the ring frame 20 and transfer of the adhesive layer 3 when the adhesive tape 10 for workpiece processing is peeled off from the ring frame 20 after dicing. In addition, for example, when grinding the semiconductor wafer 50, it is possible to appropriately follow steps such as the circuits 51 and electrodes on the surface of the semiconductor wafer 50, so that it is possible to suppress adhesive residue on the peripheral edge of the circuit surface and transfer of the adhesive layer 3 to the thinned semiconductor wafer 50' when the adhesive tape 10 for workpiece processing is peeled off from the thinned semiconductor wafer 50'.

[0089] [(Meth)acrylic acid ester copolymer (A2) with photosensitive carbon-carbon double bonds introduced into the side chain] As described above, the (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced in the side chain can be obtained by copolymerizing the functional group-containing monomer to the functional group introduced in the side chain of the (meth)acrylic acid ester copolymer base polymer (BP) and then adding a compound (active energy ray reactive compound) having a functional group capable of undergoing an addition reaction with the functional group and a carbon-carbon double bond. Examples of such active energy ray reactive compounds include compounds having an isocyanate group and a carbon-carbon double bond, compounds having a carboxyl group and a carbon-carbon double bond, compounds having a glycidyl group and a carbon-carbon double bond, compounds having an amino group and a carbon-carbon double bond, etc. These radiation reactive compounds may be used alone or in combination.

[0090] Specific examples of the above-mentioned addition reaction include, for example, (1) a method in which a hydroxyl group-containing monomer is used as a functional group-containing monomer component of the binary or more (meth)acrylic acid ester copolymer base polymer (BP) and the hydroxyl group is subjected to an addition reaction with an isocyanate group of a compound having an isocyanate group and a carbon-carbon double bond (active energy ray-reactive compound); (2) a method in which a carboxyl group-containing monomer is used as a functional group-containing monomer component of the above-mentioned base polymer (BP) and the carboxyl group is subjected to an addition reaction with a compound having a glycidyl group and a carbon-carbon double bond (active energy ray-reactive compound); (3) a method of using a glycidyl group-containing monomer as a functional group-containing monomer component of the base polymer (BP) and subjecting the glycidyl group to an addition reaction with a carboxyl group of a compound having a carboxyl group and a carbon-carbon double bond (active energy ray reactive compound); and (4) a method of using an amino group-containing monomer as a functional group-containing monomer component of the base polymer (BP) and subjecting the amino group to an addition reaction with an isocyanate group and an isocyanate group of a compound having a carbon-carbon double bond (active energy ray reactive compound).

[0091] Among the above-mentioned addition reactions, from the viewpoint of the ease of reaction tracking (stability of control) and technical difficulty, a method of using a hydroxyl group-containing monomer as a functional group-containing monomer component of the binary or more (meth)acrylic acid ester copolymer base polymer (BP), and adding the hydroxyl group to an isocyanate group of a compound (active energy ray reactive compound) having an isocyanate group and a carbon-carbon double bond is the most suitable. Examples of such compounds (active energy ray reactive compounds) having an isocyanate group and a carbon-carbon double bond include isocyanate compounds having a (meth)acryloyloxy group. Specific examples include 2-methacryloyloxyethyl isocyanate, 4-methacryloyloxy-n-butyl isocyanate, 2-acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and the like. Among these, 2-methacryloyloxyethyl isocyanate is preferred from the viewpoint of versatility.

[0092] In the above addition reaction, it is preferable to use a polymerization inhibitor so as to maintain the reactivity of the carbon-carbon double bond to active energy rays. As such a polymerization inhibitor, a quinone-based polymerization inhibitor such as hydroquinone monomethyl ether is preferable. The amount of the polymerization inhibitor is not particularly limited, but is preferably in the range of 0.01 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the binary or higher (meth)acrylic acid ester copolymer base polymer (BP).

[0093] When the above-mentioned addition reaction is carried out, (1) the functional groups of the above-mentioned (meth)acrylic acid ester copolymer (A2) are crosslinked as reaction sites by a crosslinking agent added later to further increase the molecular weight, and (2) in order to improve the initial adhesion between the active energy ray curable adhesive layer 3 and the workpiece after the crosslinking reaction, i.e., the adhesive strength of the adhesive tape 10 for workpiece processing to the workpiece before irradiation with active energy rays, it is preferable to allow functional groups to remain in the adhesive composition after the crosslinking reaction. On the other hand, it is also necessary to introduce photosensitive carbon-carbon double bonds to the binary or more (meth)acrylic acid ester copolymer base polymer (BP) in an appropriate concentration range so that the adhesive layer 3 hardens and shrinks to sufficiently reduce the adhesive strength when the adhesive tape 10 for workpiece processing is irradiated with active energy rays after the workpiece processing, thereby facilitating peeling from the workpiece. It is necessary to take these two viewpoints into consideration, for example, when an isocyanate compound having a (meth)acryloyloxy group is subjected to an addition reaction with a (meth)acrylic acid ester copolymer base polymer (BP) having a hydroxyl group in the side chain, it is preferable to use an amount of the isocyanate compound having a (meth)acryloyloxy group in which the ratio is in the range of 22 mol% to 99 mol% based on the total mole amount of the hydroxyl group-containing monomer components, which are the copolymer monomer components of the base polymer (BP), for the addition reaction. More preferably, it is in the range of 40 mol% to 90 mol%, and even more preferably, it is in the range of 50 mol% to 85 mol%.

[0094] The (meth)acrylic acid ester copolymer (A2) in which a photosensitive carbon-carbon double bond is introduced into the side chain of the binary or more (meth)acrylic acid ester copolymer base polymer (BP) of the present embodiment is obtained by subjecting a mixture of the above n-butyl acrylate (n-BA) monomer, the above functional group-containing monomer, and, if necessary, one or more monomers selected from the above monomers other than these two monomers, blended in a predetermined amount as copolymer monomer components, to polymerization to synthesize the base polymer (BP), and then subjecting the base polymer (BP) to an addition reaction with an active energy ray-reactive compound in the presence of an organometallic catalyst. The polymerization can be performed by any method such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, etc. The weight average molecular weight (Mw) of the above (meth)acrylic acid ester copolymer base polymer (A2) is preferably 100,000 or more from the viewpoint of improving the cohesive force of the active energy ray-curable adhesive layer 3, and is preferably 1.5 million or less from the viewpoint of the suitability of applying the solution of the adhesive composition of the active energy ray-curable adhesive layer 3. That is, the weight average molecular weight (Mw) is preferably in the range of 100,000 to 1,500,000, and more preferably in the range of 300,000 to 1,000,000. Here, the weight average molecular weight (Mw) is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0095] The acid value of the (meth)acrylic acid ester copolymer (A2) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, and may be 0 mgKOH / g, but is preferably 1.2 mgKOH / g or more from the viewpoint of improving the adhesion between the intermediate layer 2 and the active energy ray curable adhesive layer 3 and the adhesive strength of the adhesive tape 10 for workpiece processing to the work before irradiation with active energy rays, and is preferably 17.8 mgKOH / g or less from the viewpoint of reducing the adhesive strength of the adhesive tape 10 for workpiece processing to the work after irradiation with active energy rays. That is, the acid value is preferably in the range of 1.2 mgKOH / g or more and 17.8 mgKOH / g or less.

[0096] Furthermore, the hydroxyl value of the (meth)acrylic acid ester copolymer (A2) is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but from the viewpoints of improving the adhesion between the intermediate layer 2 and the active energy ray-curable adhesive layer 3, improving the cohesive strength of the adhesive layer 3, and controlling the adhesive strength of the adhesive tape 10 for work processing to a work before and after irradiation of the work with active energy rays, it is preferably in the range of 10.2 mgKOH / g or more and 79.2 mgKOH / g or less.

[0097] Furthermore, the carbon-carbon double bond concentration of the (meth)acrylic acid ester copolymer (A2) (carbon-carbon double bond equivalent per 1 g of solid content of (meth)acrylic acid ester copolymer (A2)) may be a concentration at which sufficient adhesive strength reduction effect is obtained in the pressure-sensitive adhesive layer 3 after irradiation with active energy rays, and is not unique, depending on the use conditions such as the amount of irradiation with active energy rays, but the carbon-carbon double bond concentration is preferably in the range of 0.59 meq / g to 1.60 meq / g, more preferably in the range of 0.59 meq / g to 1.49 meq / g, and particularly preferably in the range of 0.59 meq / g to 1.29 meq / g from the viewpoint of the balance between the effect and the economical efficiency. If the carbon-carbon double bond concentration is less than 0.59 meq / g, the adhesive strength reduction effect in the pressure-sensitive adhesive layer 3 after irradiation with active energy rays becomes small, so that when peeling off the processed work from the pressure-sensitive adhesive tape 10 for work processing, peeling becomes difficult, and there is a risk of increasing defects such as damage to the processed work. On the other hand, if the carbon-carbon double bond concentration exceeds 1.60 meq / g, the effect gradually saturates, which is not preferable from the viewpoint of economic efficiency. In addition, depending on the copolymerization composition of the (meth)acrylic acid ester copolymer (A2), gelation may occur during the addition reaction, making synthesis difficult, or the adhesion between the intermediate layer 2 and the active energy ray curable pressure-sensitive adhesive layer 3 may become insufficient. When checking the carbon-carbon double bond concentration of the (meth)acrylic acid ester copolymer (A2), for example, the iodine value of the (meth)acrylic acid ester copolymer (A2) may be measured to calculate the carbon-carbon double bond concentration.

[0098] [Crosslinking agent] The adhesive composition constituting the active energy ray curable adhesive layer 3 of the present embodiment contains a crosslinking agent capable of reacting with the functional group of the (meth)acrylic acid ester copolymer (A2) in order to increase the molecular weight of the (meth)acrylic acid ester copolymer (A2) and improve the cohesive strength of the adhesive layer 3. There are no particular limitations on such crosslinking agents, and known crosslinking agents having functional groups capable of reacting with the functional groups of the (meth)acrylic acid ester copolymer (A2), i.e., typically, hydroxyl groups or carboxyl groups introduced as necessary, can be used. Specific examples of such crosslinking agents include polyisocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, aziridine-based crosslinking agents, melamine resin-based crosslinking agents, urea resin-based crosslinking agents, acid anhydride compound-based crosslinking agents, polyamine-based crosslinking agents, and carboxyl group-containing polymer-based crosslinking agents. Among these, from the viewpoints of reactivity and versatility, it is preferable to use polyisocyanate-based crosslinking agents, epoxy-based crosslinking agents, or metal chelate-based crosslinking agents, and it is more preferable to use polyisocyanate-based crosslinking agents. These crosslinking agents may be used alone or in combination of two or more. The amount of the crosslinking agent is preferably in the range of 0.01 to 10.0 parts by mass, more preferably in the range of 0.1 to 5.0 parts by mass, and particularly preferably in the range of 0.2 to 1.0 parts by mass, relative to 100 parts by mass of the solid content of the (meth)acrylic acid ester copolymer (A2).

[0099] Examples of the polyisocyanate-based crosslinking agent and epoxy-based crosslinking agent include the same agents as those exemplified above as the crosslinking agent for the intermediate layer 2. In addition, the metal-based chelate crosslinking agent is preferably one capable of crosslinking hydroxyl groups, and specific examples thereof include titanium chelate compounds having Ti as the central metal and zirconium chelate compounds having Zr as the central metal.

[0100] Among the above crosslinking agents, polyisocyanate-based crosslinking agents such as a polyisocyanate compound having an isocyanurate ring, an adduct polyisocyanate compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, and an adduct polyisocyanate compound obtained by reacting trimethylolpropane with tolylene diisocyanate can be preferably used.

[0101] In the present embodiment, for example, when a binary or higher (meth)acrylic acid ester copolymer containing n-butyl acrylate (n-BA) and 2-hydroxyethyl acrylate (2-HEA) as copolymer monomer components is used as the base polymer of the (meth)acrylic acid ester copolymer (A2), and the above-mentioned polyisocyanate-based crosslinking agent is used as the crosslinking agent, the equivalent ratio (NCO / OH) of the isocyanate group (NCO) of the polyisocyanate-based crosslinking agent to the hydroxyl group (OH) of the (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced into its side chain in the entire pressure-sensitive adhesive composition excluding the photopolymerization initiator described below is not particularly limited as long as it is within a range that does not impede the effects of the present invention, but is preferably within a range of 0.005 to 0.338 from the viewpoints of the cohesive strength of the pressure-sensitive adhesive layer 3, the adhesion between the intermediate layer 2 and the active energy ray-curable pressure-sensitive adhesive layer 3, control of the adhesive strength, and the like. From the same viewpoint, the residual hydroxyl group concentration in the entire pressure-sensitive adhesive composition (excluding the photopolymerization initiator) after the crosslinking reaction with the polyisocyanate-based crosslinking agent is preferably in the range of 0.04 mmol / g or more and 1.62 mmol / g or less, and further, the carbon-carbon double bond concentration is preferably in the range of 0.58 meq / g or more and 1.48 meq / g or less.

[0102] [Photopolymerization initiator] The adhesive composition constituting the active energy ray-curable adhesive layer 3 of the present embodiment contains a photopolymerization initiator that generates radicals by irradiation with active energy rays. The photopolymerization initiator senses the irradiation of active energy rays to the adhesive composition constituting the active energy ray-curable adhesive layer 3, generates radicals, and starts a crosslinking reaction of the photosensitive carbon-carbon double bonds introduced into the side chains of the (meth)acrylic acid ester copolymer (A2).

[0103] The photopolymerization initiator is not particularly limited, and a conventionally known one can be used. For example, an alkylphenone radical polymerization initiator, an acylphosphine oxide radical polymerization initiator, an oxime ester radical polymerization initiator, etc. can be mentioned. Examples of the alkylphenone radical polymerization initiator include a benzyl methyl ketal radical polymerization initiator, an α-hydroxyalkylphenone radical polymerization initiator, an aminoalkylphenone radical polymerization initiator, etc. Specific examples of the benzyl methyl ketal radical polymerization initiator include 2,2'-dimethoxy-1,2-diphenylethan-1-one (for example, trade name: Omnirad651, manufactured by IGM Resins BV). Specific examples of the α-hydroxyalkylphenone radical polymerization initiator include 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Omnirad1173, manufactured by IGM Resins BV), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad184, manufactured by IGM Resins BV), 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (trade name: Omnirad2959, manufactured by IGM Resins BV), and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one (trade name: Omnirad127, manufactured by IGM Resins BV). Specific examples of the aminoalkylphenone radical polymerization initiator include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad907, manufactured by IGM Resins BV) and 2-benzylmethyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone (trade name: Omnirad369, manufactured by IGM Resins BV).Specific examples of the acylphosphine oxide radical polymerization initiator include 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: OmniradTPO, manufactured by IGM Resins BV), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (trade name: Omnirad819, manufactured by IGM Resins BV), and examples of the oxime ester radical polymerization initiator include (2E)-2-(benzoyloxyimino)-1-[4-(phenylthio)phenyl]octan-1-one (trade name: OmniradOXE-01, manufactured by IGM Resins BV). These photopolymerization initiators may be used alone or in combination of two or more.

[0104] The amount of the photopolymerization initiator added is preferably in the range of 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the solid content of the (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced in the side chain. If the amount of the photopolymerization initiator added is less than 0.1 parts by mass, the photoreactivity to active energy rays is insufficient, so that even if the (meth)acrylic acid ester copolymer (A2) is irradiated with active energy rays, the photoradical crosslinking reaction does not occur sufficiently, and as a result, the adhesive strength reducing effect in the adhesive layer 3 after irradiation with active energy rays is reduced, and when peeling off the processed work from the adhesive tape 10 for work processing, peeling becomes difficult, and there is a risk of increasing defects such as damage to the processed work. On the other hand, if the amount of the photopolymerization initiator added exceeds 10.0 parts by mass, the effect is saturated, which is not preferable from the viewpoint of economy. In addition, depending on the type of photopolymerization initiator, the adhesive layer 3 may turn yellow and have a poor appearance.

[0105] Furthermore, as a sensitizer for such a photopolymerization initiator, a compound such as dimethylaminoethyl methacrylate or isoamyl 4-dimethylaminobenzoate may be added to the above-mentioned pressure-sensitive adhesive composition.

[0106] [others] The adhesive composition constituting the active energy ray-curable adhesive layer 3 of the present embodiment may contain additives such as polyfunctional acrylic monomers, polyfunctional acrylic oligomers, tackifiers, fillers, antioxidants, colorants, flame retardants, antistatic agents, surfactants, silane coupling agents, and leveling agents, as necessary, within the scope that does not impair the effects of the present invention.

[0107] Thickness The thickness of the active energy ray curable adhesive layer 3 is not particularly limited as long as it is within a range that does not impede the effects of the present invention, and may be appropriately adjusted depending on the processing of the work, but from the viewpoints of adhesion between the intermediate layer 2 and the adhesive layer 3, improving the adhesive strength of the adhesive tape 10 for work processing to the work before irradiation with active energy rays and reducing the adhesive strength after irradiation with active energy rays, it is preferably 5 μm or more, and from the viewpoints of suitability for applying and drying the solution of the adhesive composition of the adhesive layer 3 and economic efficiency, it is preferably 150 μm or less. That is, the thickness of the adhesive layer 3 is preferably in the range of 5 μm to 150 μm, and more preferably in the range of 8 μm to 50 μm.

[0108] (Adhesive tape for workpiece processing) The adhesive tape 10 for workpiece processing according to the present embodiment has a structure including a base film 1 made of a polyester resin composition, an intermediate layer 2, and an active energy ray curable adhesive layer 3 in this order. Usually, a release liner is provided on the surface of the adhesive layer 3 opposite to the surface in contact with the intermediate layer 2. The release liner is not particularly limited, but examples thereof include synthetic resins such as polyethylene, polypropylene, and polyethylene terephthalate, and papers. In addition, the surface of the release liner may be subjected to a release treatment using a silicone release agent, a long-chain alkyl release agent, a fluorine release agent, or the like, in order to enhance the releasability of the adhesive layer 3. The thickness of the release liner is not particularly limited, but a release liner in the range of 10 μm to 200 μm can be suitably used.

[0109] The manufacturing method of the adhesive tape 10 for workpiece processing is not particularly limited, but for example, it can be manufactured by the following method. First, a base film 1 made of a polyester resin composition is prepared. Next, a solution of the resin composition for the intermediate layer 2, which is a material for forming the intermediate layer 2, is prepared. The solution of the resin composition can be prepared, for example, by uniformly mixing and stirring the (meth)acrylic acid ester copolymer (A1), which is a component of the intermediate layer 2, the crosslinking agent, and the dilution solvent. As the solvent, for example, a general-purpose organic solvent such as toluene or ethyl acetate can be used.

[0110] Next, the solution of the resin composition for the intermediate layer 2 is applied onto the substrate film 1 and dried to form an intermediate layer 2 of a predetermined thickness. The application method is not particularly limited, and for example, a die coater, a comma coater (registered trademark), a gravure coater, a roll coater, a reverse coater, etc. are usable for application. In addition, the drying conditions are not particularly limited, and for example, the drying temperature is preferably within a range of 80°C to 150°C, and the drying time is preferably within a range of 0.5 minutes to 5 minutes. Next, the release-treated surface of a release liner is attached to the exposed surface of the intermediate layer 2 formed on the substrate film 1.

[0111] Next, a release liner is prepared, and a solution of the adhesive composition for the adhesive layer 3, which is a material for forming the adhesive layer 3, is prepared. The solution of the adhesive composition can be prepared, for example, by uniformly mixing and stirring the (meth)acrylic acid ester copolymer (A2), a crosslinking agent, a photopolymerization initiator, and a dilution solvent, which are components of the adhesive layer 3. As the solvent, for example, a general-purpose organic solvent such as toluene or ethyl acetate can be used.

[0112] Next, the solution of the adhesive composition for the adhesive layer 3 is applied to the release-treated surface of the release liner and dried to form an adhesive layer 3 of a predetermined thickness. The application method is not particularly limited, and application can be performed by the same method as for the intermediate layer 2. Furthermore, the drying conditions are not particularly limited, and drying can be performed under the same conditions as for the intermediate layer 2. Then, the surface of the intermediate layer 2 formed on the previously prepared base film 1 from which the release liner has been peeled is attached to the exposed surface of the adhesive layer 3 formed on the release-treated surface of the release liner to form a laminate.

[0113] Finally, the laminate is aged for 72 hours in an environment of, for example, 40° C. to react the (meth)acrylic acid ester copolymer of the intermediate layer 2 and the adhesive layer 3 with the crosslinking agent, thereby crosslinking and curing. Through the above steps, a workpiece processing adhesive tape 10 can be produced, which comprises, in order from the substrate film side, an intermediate layer 2, an active energy ray curable adhesive layer 3, and a release liner on a substrate film 1 made of a polyester resin composition. It is also possible to age the intermediate layer 2 and the adhesive layer 3 separately, and then bond them together to form a laminate. In the present invention, a laminate having a release liner on the adhesive layer 3 is also treated as a workpiece processing adhesive tape 10.

[0114] Another method for manufacturing the above-mentioned workpiece processing adhesive tape 10 can be, for example, the following method. First, a base film 1 made of a polyester resin composition is prepared. Next, a solution of a resin composition for the intermediate layer 2, which is a material for forming the intermediate layer 2, and a solution of an adhesive composition for the adhesive layer 3, which is a material for forming the adhesive layer 3, are prepared. Next, using a die coater having two discharge ports, the above solutions are simultaneously extruded and coated on the base film 1 in the order of the intermediate layer 2 and the adhesive layer 3 from the base film side by a wet-on-wet coating method, and then dried to form the intermediate layer 2 and the adhesive layer 3 of a predetermined thickness. Then, the release-treated surface side of a release liner is attached to the exposed surface of the above-mentioned adhesive layer 3 to form a laminate.

[0115] Finally, the laminate is aged for 72 hours in an environment of, for example, 40° C. to react the (meth)acrylic acid ester copolymer of the intermediate layer 2 and the adhesive layer 3 with the crosslinking agent, thereby crosslinking and curing. Through the above steps, an adhesive tape 10 for work processing can be produced which comprises, in order from the base film side, the intermediate layer 2, the active energy ray-curable adhesive layer 3, and a release liner on a base film 1 made of a polyester resin composition.

[0116] In the adhesive tape 10 for workpiece processing, the sum of the thicknesses of the intermediate layer 2 and the active energy ray curable adhesive layer 3 is not particularly limited as long as it does not impede the effects of the present invention, and may be appropriately adjusted according to the processing of the workpiece, but is preferably in the range of 10 μm to 300 μm, more preferably in the range of 13 μm to 150 μm. More specifically, for example, when dicing a brittle workpiece such as a glass substrate 30 or a hard workpiece such as a sapphire glass substrate, the sum of the thicknesses is preferably in the range of 13 μm to 40 μm. Also, for example, when grinding a semiconductor wafer having a circuit formed on its surface, the sum of the thicknesses is preferably in the range of 20 μm to 135 μm.

[0117] The adhesive tape 10 for workpiece processing must have a high initial adhesive strength so that the workpiece can be firmly held and fixed on the active energy ray-curable adhesive layer 3 without moving during processing of the workpiece. On the other hand, after the predetermined processing is completed, the active energy ray-curable adhesive layer 3 must be cured and shrunk by irradiation with active energy rays, and its adhesive strength must be significantly reduced so that the processed workpiece can be easily peeled off from the adhesive tape 10 for workpiece processing.

[0118] Examples of the active energy rays include ultraviolet rays, visible light, infrared rays, electron beams, β rays, and γ rays. Among these active energy rays, ultraviolet rays (UV) and electron beams (EB) are preferred, and ultraviolet rays (UV) are particularly preferred. The light source for irradiating the ultraviolet rays (UV) is not particularly limited, and examples of the light source that can be used include black lights, ultraviolet fluorescent lamps, low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, extra-high pressure mercury lamps, carbon arc lamps, metal halide lamps, and xenon lamps. In addition, ArF excimer lasers, KrF excimer lasers, excimer lamps, synchrotron radiation, and the like can also be used. The irradiation dose of the ultraviolet rays (UV) is not particularly limited, and can be, for example, 100 mJ / cm. 2 More than 2,000mJ / cm 2 The range is preferably 300 mJ / cm 2 More than 1,000mJ / cm 2 The following range is more preferable:

[0119] The adhesive strength (initial adhesive strength) of the adhesive tape 10 for workpiece processing to the glass plate before ultraviolet irradiation is preferably in the range of 5.0 N / 25 mm to 26.0 N / 25 mm, and more preferably in the range of 19.0 N / 25 mm to 25.0 N / 25 mm. If the adhesive strength to the glass plate before ultraviolet irradiation is less than 5.0 N / 25 mm, for example, when dicing the glass substrate 30, it is difficult to hold and fix the glass substrate 30 well on the adhesive layer 3 of the adhesive tape 10 for workpiece processing, so that scattering and positional shift of the glass chip 30a, chipping of the glass chip 30a due to positional shift, etc. may not be sufficiently suppressed. On the other hand, if the adhesive strength to the glass plate before ultraviolet irradiation exceeds 25.0 N / 25 mm, the glass chip 30a is held excessively strongly on the adhesive layer 3, so that the adhesive strength of the adhesive tape 10 for workpiece processing after ultraviolet irradiation is not sufficiently reduced, and the glass chip 30a may not be picked up well.

[0120] In addition, the adhesive strength of the adhesive tape 10 for workpiece processing to the glass plate after ultraviolet irradiation is preferably in the range of 0.01 N / 25 mm or more and 0.5 N / 25 mm or less, and more preferably in the range of 0.02 N / 25 mm or more and 0.25 N / 25 mm or less. If the adhesive strength of the adhesive tape 10 for workpiece processing to the glass plate after ultraviolet irradiation is less than 0.01 N / 25 mm, for example, in the stage from dicing the glass substrate 30 to picking up the glass chip 30a from the adhesive tape 10 for workpiece processing, the glass chip 30a may be unintentionally peeled off or shifted from the adhesive tape 10 for workpiece processing, and therefore, it may not be possible to pick up the glass chip 30a well. On the other hand, if the adhesive strength of the adhesive tape 10 for workpiece processing after ultraviolet irradiation exceeds 0.5 N / 25 mm, for example, when picking up the glass chip 30a individually, the adhesive strength is not sufficiently reduced, so that the glass chip 30a may be damaged or may not be picked up well. Even if it is possible to pick up the glass chip 30a, there is a risk of glue residue being generated.

[0121] The adhesive strength in the present invention is the adhesive strength (N / 25 mm) measured by the 180° peeling method in accordance with JIS Z0237:2009, and the details of the measurement method are as described in the test method described later. The adhesive strength after ultraviolet irradiation was measured by irradiating the adhesive tape 10 for work processing with ultraviolet light from the substrate film 1 side of the adhesive tape 10 with an irradiation intensity of 75 mW / cm using a high-pressure mercury lamp as a light source. 2 The accumulated light intensity is 300mJ / cm 2 The measurements were taken after irradiating the material with ultraviolet (UV) light having a central wavelength of 365 nm so that the

[0122] Furthermore, the adhesive strength (initial adhesive strength) of the adhesive tape 10 for workpiece processing to a stainless steel plate (SUS304BA plate) before ultraviolet irradiation is preferably in the range of 5.0 N / 25 mm to 26.0 N / 25 mm, more preferably in the range of 19.0 N / 25 mm to 25.0 N / 25 mm. If the adhesive strength to the stainless steel plate (SUS304BA plate) before ultraviolet irradiation is less than 5.0 N / 25 mm, for example, when dicing a glass substrate 30, the adhesive tape 10 for workpiece processing may not withstand the load or water pressure of the dicing blade 40 or cleaning water, and may peel off or shift from the SUS ring frame 20. In addition, for example, when grinding a semiconductor wafer 50, grinding water may penetrate into the interface between the semiconductor wafer 50 and the adhesive layer 3. On the other hand, if the adhesive strength before ultraviolet irradiation to the stainless steel plate (SUS304BA plate) exceeds 25.0 N / 25 mm, for example, in the dicing process of the workpiece, the SUS ring frame 20 is held and fixed excessively strongly on the adhesive layer 3, so that when the adhesive tape 10 for workpiece processing that is no longer needed is peeled off from the ring frame after the required process, the adhesive layer 3 may be transferred to the SUS ring frame. Also, in the grinding process of the semiconductor wafer 50, the semiconductor wafer 50 is held and fixed excessively strongly on the adhesive layer 3, so that the adhesive strength of the adhesive tape 10 for workpiece processing after ultraviolet irradiation is not sufficiently reduced, so that when the adhesive tape 10 for workpiece processing is peeled off from the thinned semiconductor wafer 50' after grinding, the adhesive layer 3 may be transferred or leave a glue residue on the surface of the thinned semiconductor wafer 50'.

[0123] Furthermore, the adhesive strength of the adhesive tape 10 for work processing to a stainless steel plate (SUS304BA plate) after ultraviolet irradiation is preferably in the range of 0.01 N / 25 mm to 0.5 N / 25 mm, more preferably in the range of 0.02 N / 25 mm to 0.25 N / 25 mm. When the adhesive strength of the adhesive tape 10 for work processing to a stainless steel plate (SUS304BA plate) after ultraviolet irradiation is in the above range, for example, when the adhesive tape 10 for work processing to a stainless steel plate (SUS304BA plate) is peeled off from the thinned semiconductor wafer 50' after grinding the semiconductor wafer 50, the adhesive tape 10 for work processing can be easily peeled off without transferring or leaving adhesive residue on the surface of the thinned semiconductor wafer 50' and without damaging the thinned wafer 50'.

[0124] As described above, according to the adhesive tape 10 for workpiece processing of the present invention, the base film 1 made of a polyester resin composition and the active energy ray curable adhesive layer 3 are well adhered to each other through the intermediate layer 2 in both states before and after the irradiation of active energy rays, so that, for example, even when used as a backgrind tape for extremely thinning a semiconductor wafer, the active energy ray curable adhesive layer can be peeled off without being transferred to the semiconductor wafer during peeling, and even when used as a dicing tape for cutting a brittle workpiece such as a glass substrate or a hard workpiece such as a sapphire glass substrate, the tape does not peel off from the ring frame during the process, and can be peeled off without leaving any adhesive residue when peeled off from the ring frame, providing not only excellent workability but also excellent workpiece processing quality. The adhesive tape 10 for workpiece processing of the present embodiment can be suitably used for processing and transporting workpieces such as semiconductor wafers and optical members as well as ceramics and other electronic device members. EXAMPLES

[0125] Next, the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0126] 1. Preparation of a solution of the resin composition for the intermediate layer As solutions of resin compositions for the intermediate layer 2 of the adhesive tape 10 for work processing, solutions of resin compositions (A1-a) to (A1-s) containing the following (meth)acrylic acid ester copolymers (A1-a') to (A1-s'), respectively, were prepared.

[0127] First, as copolymer monomer components for synthesizing the (meth)acrylic acid ester copolymer (A1), · Methyl acrylate (MA, molecular weight: 86.04, homopolymer Tg: 10°C); · Methacrylic acid (MAA, molecular weight: 86.06: homopolymer Tg: 228°C); · Acrylic acid (AA, molecular weight: 72.06: homopolymer Tg: 106°C); · 2-Ethylhexyl acrylate (2-EHA, molecular weight: 184.3, homopolymer Tg: -70°C); · n-Butyl acrylate (n-BA, molecular weight: 128.17, homopolymer Tg: -54°C); · Ethyl acrylate (EA, molecular weight: 100.12, homopolymer Tg: -22°C); 2-Hydroxyethyl acrylate (2-HEA, molecular weight: 116.12, homopolymer Tg: -15°C) was prepared.

[0128] Furthermore, a TDI-based polyisocyanate crosslinking agent manufactured by Tosoh Corporation (product name: Coronate L-45E, solids concentration: 45 mass%, isocyanate group content in solution: 8.05 mass%, isocyanate group content in solids: 17.89 mass%, calculated number of isocyanate groups: average 2.8 / molecule, molecular weight: 656.64) was prepared as the crosslinking agent.

[0129] (Solution of resin composition (A1-a) for intermediate layer) As copolymer monomer components, 2-ethylhexyl acrylate (2-EHA), methyl acrylate (MA), and methacrylic acid (MAA) were prepared. These copolymer monomer components were mixed to a copolymerization ratio of 2-EHA / MA / MAA = 50 parts by mass / 47 parts by mass / 3 parts by mass (= 271.30 mmol / 546.26 mmol / 34.86 mmol), and a solution of (meth)acrylic acid ester copolymer (A1-a') (solid content concentration: 35 mass%, weight average molecular weight Mw: 400,000, solid acid value: 19.6 mg KOH / g) was synthesized by solution radical polymerization using ethyl acetate as a solvent and azobisisobutyronitrile (AIBN) as an initiator. The Tg of the obtained (meth)acrylic acid ester copolymer (A1-a') calculated from the Fox formula was -34 ° C.

[0130] Next, 286 parts by mass (100 parts by mass equivalent to solids content) of this (meth)acrylic acid ester copolymer (A1-a') solution was mixed with 0.45 parts by mass (0.20 parts by mass equivalent to solids content, 0.30 mmol) of a TDI-based polyisocyanate crosslinking agent manufactured by Tosoh Corporation (product name: Coronate L-45E, solids concentration: 45% by mass) as a crosslinking agent, diluted with ethyl acetate, and stirred to prepare a solution of resin composition (A1-a) for intermediate layer 2 with a solids concentration of 30% by mass.

[0131] (Solutions of Resin Compositions (A1-b) to (A1-s) for Intermediate Layer) Solutions of (meth)acrylic acid ester copolymers (A1-b') to (A1-s') were synthesized in the same manner as for (meth)acrylic acid ester copolymer (A1-a'), except that the copolymerization ratio and copolymer monomer components of the copolymer monomer components were appropriately changed as shown in Tables 1 to 4 and 9, respectively. The glass transition temperature (Tg), weight average molecular weight (Mw), solid acid value, and solid hydroxyl value of the synthesized (meth)acrylic acid ester copolymers (A1-b') to (A1-s') were as shown in Tables 1 to 4 and 9, respectively. Next, using solutions of these (meth)acrylic acid ester copolymers, 286 parts by mass (100 parts by mass in terms of solid content) of each of the (meth)acrylic acid ester copolymers (A1-b') to (A1-s') were mixed with 0.45 parts by mass (0.20 parts by mass in terms of solid content, 0.30 mmol) of a TDI-based polyisocyanate-based crosslinking agent manufactured by Tosoh Corporation (product name: Coronate L-45E, solid content concentration: 45% by mass) as a crosslinking agent, diluted with ethyl acetate, and stirred to prepare solutions of resin compositions (A1-b) to (A1-s) for the intermediate layer 2 with a solid content concentration of 30% by mass.

[0132] 2. Preparation of a solution of the adhesive composition As adhesive compositions for the active energy ray-curable adhesive layer 3 of the adhesive tape 10 for work processing, adhesive compositions (A2-a) to (A2-j) were synthesized, each containing (meth)acrylic acid ester copolymers (A2-a') to (A2-j'), in which a photosensitive carbon-carbon double bond has been introduced into the side chain of a (meth)acrylic acid ester copolymer base polymer (BP) having n-butyl acrylate (n-BA) as the main copolymer monomer component, as shown below.

[0133] First, as a copolymer monomer component for synthesizing a (meth)acrylic acid ester copolymer base polymer (BP) having n-butyl acrylate (n-BA) as the main copolymer monomer component, · Methyl methacrylate (MMA, molecular weight: 100.12, homopolymer Tg: 105°C); · n-Butyl acrylate (n-BA, molecular weight: 128.17, homopolymer Tg: -54°C); · 2-Ethylhexyl acrylate (2-EHA, molecular weight: 184.3, Tg: -70°C); · 2-Hydroxyethyl acrylate (2-HEA, molecular weight: 116.12, Tg: -15°C); Methacrylic acid (MAA, molecular weight: 86.06, Tg: 228℃) was prepared.

[0134] Furthermore, a TDI-based polyisocyanate crosslinking agent manufactured by Tosoh Corporation (product name: Coronate L-45E, solids concentration: 45 mass%, isocyanate group content in solution: 8.05 mass%, isocyanate group content in solids: 17.89 mass%, calculated number of isocyanate groups: average 2.8 / molecule, molecular weight: 656.64) was prepared as the crosslinking agent.

[0135] (Solution of adhesive composition (A2-a) for active energy ray-curable adhesive layer) As copolymerization monomer components, n-butyl acrylate (n-BA), 2-hydroxyethyl acrylate (2-HEA), and methacrylic acid (MAA) were prepared. These copolymerization monomer components were mixed to a copolymerization ratio of n-BA / 2-HEA / MAA = 76.8 parts by mass / 20.2 parts by mass / 3.0 parts by mass (= 599.20 mmol / 173.96 mmol / 34.86 mmol), and a solution of (meth)acrylic acid ester copolymer base polymer (BP-a) with n-butyl acrylate (n-BA) as the main component of the copolymer monomer was synthesized by solution radical polymerization using ethyl acetate as a solvent and azobisisobutyronitrile (AIBN) as an initiator. The Tg of the obtained (meth)acrylic acid ester copolymer base polymer (BP-a) calculated from the Fox formula is -43 ° C.

[0136] Next, 10.0 parts by mass of 2-isocyanateethyl methacrylate having an isocyanate group and an active energy ray reactive carbon-carbon double bond manufactured by Showa Denko K.K. (trade name: Karenz MOI, molecular weight: 155.15, isocyanate group: 1 group / molecule, double bond group: 1 group / molecule) was added as an active energy ray reactive compound manufactured by Showa Denko K.K. relative to 100 parts by mass of the solid content of the (meth)acrylic acid ester copolymer base polymer (BP-a). A solution of (meth)acrylic acid ester copolymer (A2-a') with photosensitive carbon-carbon double bonds introduced into the side chain (solid concentration: 40 mass%, weight average molecular weight Mw: 400,000, solid content hydroxyl value: 55.8 mg KOH / g, solid content acid value: 17.8 mg KOH / g, carbon-carbon double bond content: 0.59 mmol / g) was synthesized by mixing 64.45 mmol (37.1 mol%) of 2-HEA and reacting it with some of the hydroxyl groups of 2-HEA. In addition, 0.05 parts by mass of hydroquinone monomethyl ether was used as a polymerization inhibitor to maintain the reactivity of the carbon-carbon double bonds in the above reaction.

[0137] Next, 250 parts by mass (100 parts by mass in terms of solid content) of the solution of the (meth)acrylic acid ester copolymer (A2-a') having a photosensitive carbon-carbon double bond in a side chain synthesized above was mixed with 1.52 parts by mass of an acylphosphine oxide-based photopolymerization initiator (product name: Omnirad819) manufactured by IGM Resins BV, and 0.45 parts by mass (0.20 parts by mass in terms of solid content, 0.30 mmol) of a TDI-based polyisocyanate-based crosslinking agent (product name: Coronate L-45E, solid content concentration: 45% by mass) manufactured by Tosoh Corporation as a crosslinking agent, and the mixture was diluted with ethyl acetate and stirred to prepare a solution of adhesive composition (A2-a) for adhesive layer 3 with a solid content concentration of 30% by mass. In the pressure-sensitive adhesive composition (A2-a) excluding the photopolymerization initiator, the equivalent ratio (NCO / OH) of the isocyanate group (NCO) of the polyisocyanate crosslinking agent to the hydroxyl group (OH) of the (meth)acrylic acid ester copolymer (A2-a') having a photosensitive carbon-carbon double bond introduced into its side chain was 0.007, the residual hydroxyl group concentration was 0.99 mmol / g, and the carbon-carbon double bond content was 0.58 mmol / g.

[0138] (Solutions of Pressure-Sensitive Adhesive Compositions (A2-b) to (A2-j) for Active Energy Ray-Curable Pressure-Sensitive Adhesive Layer) First, the copolymerization ratio and copolymer monomer components of the (meth)acrylic acid ester copolymer base polymer (BP-a) were appropriately changed as shown in Tables 4 to 6, respectively, and the other components were similarly used to synthesize solutions of (meth)acrylic acid ester copolymer base polymers (BP-b) to (BP-j). Next, the amount of 2-isocyanate ethyl methacrylate (trade name: Karenz MOI), which is an active energy ray reactive compound, was added to these (meth)acrylic acid ester copolymer base polymers (BP-b) to (BP-j) in the amounts shown in Tables 4 to 6, respectively, and the other components were similarly used to synthesize solutions of (meth)acrylic acid ester copolymers (A2-b') to (A2-j') in which photosensitive carbon-carbon double bonds were introduced into the side chains. The glass transition temperatures (Tg) of the synthesized (meth)acrylic acid ester copolymer base polymers (BP-b) to (BP-j), and the weight average molecular weights (Mw), solid content hydroxyl value, solid content acid value, and carbon-carbon double bond concentrations in the (meth)acrylic acid ester copolymers (A2-b') to (A2-j') were as shown in Tables 4 to 6. Next, an acylphosphine oxide-based photopolymerization initiator (trade name: Omnirad819) and a polyisocyanate-based crosslinking agent (trade name: Coronate L-45E) were mixed with the (meth)acrylic acid ester copolymers (A2-b') to (A2-j') having photosensitive carbon-carbon double bonds introduced into the side chains, as shown in Tables 4 to 6, respectively, and the mixture was diluted with ethyl acetate and stirred to prepare solutions of adhesive compositions (A2-b) to (A2-j) for the adhesive layer 3 having a solid content concentration of 30% by mass.

[0139] In addition, in the pressure-sensitive adhesive compositions (A2-b) to (A2-j) excluding the photopolymerization initiator, the equivalent ratios (NCO / OH) of the isocyanate groups (NCO) of the polyisocyanate-based crosslinking agent to the hydroxyl groups (OH) of the (meth)acrylic acid ester copolymers (A2-b) to (A2-j) having photosensitive carbon-carbon double bonds introduced into their side chains, the residual hydroxyl group concentrations, and the carbon-carbon double bond concentrations were as follows: (A2-b) (NCO / OH): 0.009, Residual hydroxyl group concentration: 0.99mmol / g, Carbon-carbon double bond concentration: 0.58meq / g (A2-c) (NCO / OH): 0.023, Residual hydroxyl group concentration: 0.37mmol / g, Carbon-carbon double bond concentration: 1.07meq / g (A2-d) (NCO / OH): 0.020, Residual hydroxyl group concentration: 0.42 mmol / g, Carbon-carbon double bond concentration: 1.29 meq / g (A2-e) (NCO / OH): 0.016, Residual hydroxyl group concentration: 0.52mmol / g, Carbon-carbon double bond concentration: 1.48meq / g (A2-f) (NCO / OH): 0.047, Residual hydroxyl group concentration: 0.17mmol / g, Carbon-carbon double bond concentration: 0.58meq / g (A2-g) (NCO / OH): 0.005, Residual hydroxyl group concentration: 1.62mmol / g, Carbon-carbon double bond concentration: 0.89meq / g (A2-h) (NCO / OH): 0.338, Residual hydroxyl group concentration: 0.04mmol / g, Carbon-carbon double bond concentration: 0.69meq / g (A2-i) (NCO / OH): 0.015, Residual hydroxyl group concentration: 1.38mmol / g, Carbon-carbon double bond concentration: 0.88meq / g (A2-j) (NCO / OH): 0.216, Residual hydroxyl group concentration: 0.15mmol / g, Carbon-carbon double bond concentration: 0.58meq / g

[0140] 3. Preparation of Adhesive Tape 10 for Workpiece Processing For the adhesive tapes for work processing 10(a) to 10(kk) produced in the above Examples 1 to 31 and Comparative Examples 1 to 6, the structures of the base film 1, intermediate layer 2 and active energy ray-curable adhesive layer 3 are shown in Tables 1 to 10.

[0141] Example 1 A polyethylene terephthalate (PET) film manufactured by Unitika Ltd. (product name: Emblet #100, thickness: 100 μm) was used as the base film 1, and a solution of the resin composition (A1-a) for the intermediate layer was applied thereon so that the thickness of the intermediate layer 2 after drying would be 10 μm. The solvent was then dried by heating at a temperature of 100° C. for 3 minutes, and an intermediate layer 2 was formed on the base film 1.

[0142] Next, a solution of the adhesive composition (A2-a) was applied to the release-treated surface of a release liner (product name: NS-38+A, material: polyethylene terephthalate, thickness: 38 μm) manufactured by Nakamoto Packs Co., Ltd., so that the thickness of the active energy ray-curable adhesive layer 3 after drying was 10 μm, and the solution was heated at a temperature of 100° C. for 3 minutes to dry the solvent, and then the surface of the intermediate layer 2 formed on the base film 1 was attached to the active energy ray-curable adhesive layer 3. Next, the active energy ray-curable adhesive layer 3 was crosslinked and cured by storing at a temperature of 40° C. for 72 hours to produce an adhesive tape 10(a) for work processing.

[0143] (Examples 2 to 15) Adhesive tapes 10(b) to 10(o) for work processing were prepared in the same manner as in Example 1, except that the solution of resin composition (A1-a) for intermediate layer 2 was changed to a solution of resin compositions (A1-b) to (A1-o) for intermediate layer 2 as shown in Tables 1 to 4, respectively.

[0144] (Examples 16 to 24) The solution of adhesive composition (A2-a) for the active energy ray-curable adhesive layer 3 was changed to a solution of adhesive composition (A2-b) to (A2-j) for adhesive composition 3 as shown in Tables 4 to 6, respectively, and adhesive tapes 10(p) to 10(x) for work processing were produced in the same manner as in Example 2, except that the amount of crosslinking agent in the adhesive composition was changed only in Examples 22 to 24.

[0145] (Examples 25 to 31) Adhesive tapes 10(y) to 10(ee) for work processing were prepared in the same manner as in Example 2, except that the thickness of the intermediate layer 2 and the thickness of the active energy ray-curable adhesive layer 3 were set to the thicknesses shown in Tables 7 and 8, respectively.

[0146] (Comparative Examples 1 to 4) Adhesive tapes 10(ff) to 10(ii) for work processing were prepared in the same manner as in Example 1, except that the solution of resin composition (A1-a) for intermediate layer 2 was changed to a solution of resin compositions (A1-p) to (A1-s) for intermediate layer 2 as shown in Table 9.

[0147] Comparative Example 5 As shown in Table 10, an adhesive tape for work processing 10 (jj) was produced in the same manner as in Example 1, except that the intermediate layer 2 was not provided.

[0148] Comparative Example 6 The solution of the resin composition (A1-a) for the intermediate layer 2 was prepared by dissolving an amorphous polyester resin manufactured by Toyobo Co., Ltd. (product name: Vylon 600, number average molecular weight Mn: 16,000, Tg: 47°C, hydroxyl value: 7 mgKOH / g, acid value: <2 mgKOH / g) in methyl ethyl ketone to give a solid content concentration of 30 mass %, and adding 333.3 parts by mass (100 parts by mass in terms of solid content) of a solution containing an HDI-based polyisocyanate-based crosslinking agent manufactured by Tosoh Corporation (product name: Coronate HL, solid content concentration: 75% by mass, isocyanate group content in solution: 12.8% by mass, isocyanate group content in solid content: 17.07% by mass, calculated number of isocyanate groups: average 2.6 / molecule, molecular weight: 638.75) was mixed in a ratio of 13.3 parts by mass (10 parts by mass in solid content equivalent, 15.66 mmol), and the thickness of the intermediate layer 2 was changed to 2 μm, as shown in Table 10, and an adhesive tape 10 (kk) for work processing was produced in the same manner as in Example 1.

[0149] 4. Evaluation method of adhesive tape 10 for workpiece processing The adhesive tapes 10(a) to 10(kk) for workpiece processing produced in the above Examples 1 to 31 and Comparative Examples 1 to 6 were evaluated for adhesive strength before and after UV irradiation, adhesive residue on the adherend, and adhesion of the active energy ray-curable adhesive layer, as described below.

[0150] 4.1 Measurement of adhesive strength before and after UV irradiation The adhesive tapes 10(a)-10(kk) for workpiece processing prepared in the examples and comparative examples were cut into strips of 150 mm long x 25 mm wide to prepare test samples. The MD direction (the direction in which the intermediate layer 2 and the adhesive layer 3 are applied) of the adhesive tape 10 for workpiece processing was the length direction of the test sample, and the direction perpendicular thereto was the width direction of the test sample. A glass plate and a stainless steel plate (SUS304BA plate) were prepared as adherends. In an environment of 23°C temperature and 50% humidity, the release liner was peeled off from the adhesive tape 10 for workpiece processing, the exposed surface of the adhesive layer 3 was placed on one surface of the adherend, and the two were laminated by applying a load by moving a 2 kg roller back and forth once, and left for 20 minutes. The length of the laminated portion was 80 mm. Thereafter, the adhesive tape 10 for work processing was peeled off from the adherend at a peeling speed of 300 mm / min and a peeling angle of 180° using a tensile tester according to JIS Z0237: 2009 at a peeling speed of 300 mm / min and a peeling angle of 180° to measure the adhesive strength (unit: N / 25 mm). The number of samples for measurement was three, and the average value of the three measurements was taken as the adhesive strength before ultraviolet (UV) irradiation.

[0151] Similarly to the above, the adhesive tape 10 for work processing produced in the examples and comparative examples was laminated to an adherend and left for 20 minutes, after which ultraviolet light (UV) with a central wavelength of 365 nm was irradiated from the base film 1 side of the adhesive tape 10 for work processing using a high-pressure mercury lamp to cure the adhesive layer 3. The ultraviolet light irradiation conditions were irradiation intensity: 75 mW / cm 2 , Accumulated light intensity: 300mJ / cm 2 Thereafter, the adhesive strength (unit: N / 25 mm) was measured in the same manner as above, and the average value of three measurements was taken as the adhesive strength after ultraviolet (UV) irradiation.

[0152] 4.2 Evaluation of adhesive residue The surface of the adherend after the above-mentioned adhesive strength measurement was visually observed and evaluated for the presence or absence of adhesive residue. For the glass plate, the surface was observed after the adhesive strength measurement after ultraviolet irradiation was performed. This is a hypothetical evaluation of adhesive residue on the surface of the glass chip 30a when the glass chip 30a is picked up from the adhesive tape 10 for workpiece processing irradiated with ultraviolet light after dicing of the glass substrate 30.

[0153] In addition, the stainless steel plate (SUS304BA plate) was observed on its surface before and after ultraviolet irradiation to measure the adhesive strength. The former (before ultraviolet irradiation) is a hypothetical evaluation of adhesive residue on the surface of the ring frame 20 when the outer edge portion of the adhesive tape 10 for workpiece processing that was not irradiated with ultraviolet (UV) rays is peeled off from the ring frame 20 after the dicing process is completed. The latter (after ultraviolet irradiation) 9 is a hypothetical evaluation of adhesive residue on the surface of the semiconductor wafer 50' when the adhesive tape 10 for workpiece processing that was irradiated with ultraviolet rays is peeled off from the thinned semiconductor wafer 50' after the semiconductor wafer 50 is ground.

[0154] The adhesive residue was evaluated according to the following criteria: A rating of ◯ was determined to be practically acceptable. Evaluation criteria 〇: No glue residue ×: Glue residue remains

[0155] 4.3 Evaluation of adhesion of active energy ray-curable adhesive layer (cross-cut test) First, the adhesive tape 10 for work processing produced in the examples and comparative examples was irradiated with ultraviolet light (UV) having a central wavelength of 365 nm from a high-pressure mercury lamp from the side of the base film 1 to cure the adhesive layer 3. The ultraviolet light irradiation conditions were: irradiation intensity: 75 mW / cm 2 , Accumulated light intensity: 300mJ / cm 2Next, the release liner was peeled off from the adhesive tape 10 for workpiece processing, and a grid-like cut was made from the surface of the adhesive layer 3 based on the cross-cut method of JIS K 5600-5-6:1999. The number of cuts in each direction of the grid pattern was 10, and the cut interval was 1 mm, forming 100 grid squares. After attaching a film substrate adhesive tape (product name: NO. 626050 film tape manufactured by Maxell Co., Ltd.; 180° peel adhesion strength against SUS304BA plate: 10.8 N / 25 mm) onto the formed grid squares, the adhesive layer 3 was peeled off by hand and the number of squares from which the adhesive layer 3 peeled off was counted to evaluate the adhesion between the intermediate layer 2 and the active energy ray curable adhesive layer 3. In addition, when the intermediate layer 2 is not present, the adhesion between the substrate film 1 and the active energy ray curable adhesive layer 3 is evaluated. This evaluation is a hypothetical evaluation of adhesive residue on the surface of the semiconductor wafer 50' when the adhesive tape 10 for work processing irradiated with ultraviolet rays is peeled off at high speed from the thinned semiconductor wafer 50' after grinding of the semiconductor wafer 50. In other words, if the adhesion is good, no adhesive residue will be left on the surface of the thinned semiconductor wafer 50' even if the adhesive tape 10 for work processing irradiated with ultraviolet rays is peeled off at high speed.

[0156] In addition, in the above-mentioned case where the adhesive tape 10 for workpiece processing was not irradiated with ultraviolet rays (UV), i.e., in the state before ultraviolet rays (UV) irradiation, the adhesion between the intermediate layer 2 and the active energy ray curable adhesive layer 3 was also evaluated based on the above-mentioned cross-cut method. This evaluation is a hypothetical evaluation of adhesive residue on the surface of the ring frame 20 when the outer edge portion of the adhesive tape 10 for workpiece processing that was not irradiated with ultraviolet rays (UV) is peeled off from the ring frame 20 at high speed after the dicing process is completed, for example, when the adhesive tape for workpiece processing attached to the ring frame 20 is strongly pressed by hand from the center of the tape to be peeled off. In other words, if the adhesion is good, no adhesive residue will be left on the surface of the thinned semiconductor wafer 50' even if the outer edge portion of the adhesive tape 10 for workpiece processing that was not irradiated with ultraviolet rays (UV) is peeled off from the ring frame 20 at high speed.

[0157] The adhesion was evaluated according to the following criteria: A rating of ◯ was determined to be satisfactory for practical use. ○: The number of squares where the adhesive layer peeled off out of 100 squares is 0 (0 / 100). ×: The number of squares where the adhesive layer peeled off out of 100 squares is in the range of 1 to 100 (1 / 100 to 100 / 100).

[0158] 5. Evaluation Results The results of evaluating the physical properties of the adhesive tapes 10(a) to 10(kk) for work processing produced in the above Examples 1 to 31 and Comparative Examples 1 to 6 are shown in Tables 11 to 20.

[0159] [Table 1]

[0160] [Table 2]

[0161] [Table 3]

[0162] [Table 4]

[0163] [Table 5]

[0164] [Table 6]

[0165] [Table 7]

[0166]

Table 8

[0167]

Table 9

[0168]

Table 10

[0169]

Table 11

[0170]

Table 12

[0171]

Table 13

[0172]

Table 14

[0173]

Table 15

[0174]

Table 16

[0175]

Table 17

[0176]

Table 18

[0177] [Table 19]

[0178] [Table 20]

[0179] First, as shown in Tables 11 to 18, it was confirmed that the adhesive tapes 10(a) to 10(ee) for workpiece processing of Examples 1 to 31 satisfying the requirements of the present invention can obtain favorable results in the evaluation of the adhesive strength before and after ultraviolet irradiation, the adhesive residue on the adherend, and the adhesion of the active energy ray curable adhesive layer, even when a film made of a polyester resin composition is used as the base film for the purpose of improving the processing quality of the workpiece. That is, when the adhesive tape for workpiece processing of the present invention is used as a backgrind tape for ultra-thinning a semiconductor wafer, it is possible to uniformly ultra-thin the semiconductor wafer by grinding, and when the backgrind tape is peeled off after grinding, it is possible to peel off the active energy ray curable adhesive layer without being transferred to the ultra-thinned semiconductor wafer. Furthermore, when used as a dicing tape for cutting fragile workpieces such as glass substrates or hard workpieces such as sapphire glass substrates with high quality, the dicing tape holding the workpiece does not peel off from the ring frame during the dicing process, and the chip pick-up properties after dicing are also good.It is believed that when the dicing tape is peeled off from the ring frame after pick-up is completed, it can be peeled off without leaving any glue residue on the ring frame.

[0180] In contrast, as shown in Tables 19 and 20, the adhesive tapes 10(ff) to 10(kk) for workpiece processing of Comparative Examples 1 to 6, which do not satisfy the requirements of the present invention, had acceptable levels of adhesive strength before and after UV irradiation, but were found to be inferior to the adhesive tapes 10(a) to 10(ee) for workpiece processing of Examples 1 to 31 in either the adhesive residue on the adherend or the adhesion of the active energy ray-curable adhesive layer.

[0181] Specifically, in the adhesive tape 10(ff) for workpiece processing of Comparative Example 1 and the adhesive tape 10(gg) for workpiece processing of Comparative Example 2, the content of methyl acrylate, which is a copolymer monomer component of the ternary (meth)acrylic acid ester copolymer (A1) in the intermediate layer 2, exceeds the upper limit of the claimed range, and therefore, in the evaluation of adhesive residue before ultraviolet irradiation, adhesive residue was observed on the surface of the stainless steel plate (SUS304BA plate). Furthermore, in the evaluation of adhesion by a cross-cut test after ultraviolet irradiation, the adhesive tape 10(gg) for workpiece processing of Comparative Example 2 showed more peeling of the adhesive layer than the adhesive tapes 10(a) to 10(c) for workpiece processing of Examples 1 to 3.

[0182] In addition, the adhesive tape 10(hh) for workpiece processing of Comparative Example 3 and the adhesive tape 10(ii) for workpiece processing of Comparative Example 4 have a content ratio of methacrylic acid, which is a copolymer monomer component of the ternary (meth)acrylic acid ester copolymer (A1) in the intermediate layer 2, below the lower limit of the claimed range, and therefore, in the evaluation of adhesion by cross-cut test before ultraviolet irradiation, peeling of the adhesive layer was confirmed considerably more than that of the adhesive tapes 10(b), 10(d), 10(f) and 10(g) for workpiece processing of Examples 2, 4, 6 and 7. In addition, in the evaluation of adhesive residue before ultraviolet irradiation, adhesive residue was observed on the surface of the stainless steel plate (SUS304BA plate).

[0183] Furthermore, since the adhesive tape 10 (jj) for work processing of Comparative Example 5 did not have an intermediate layer 2, when the adhesion was evaluated by a cross-cut test before exposure to ultraviolet rays, complete peeling (100 / 100) of the adhesive layer was observed.

[0184] Furthermore, the adhesive tape 10 (kk) for work processing of Comparative Example 6 used an amorphous polyester resin composition different from that of the present invention for the intermediate layer 2, but when the adhesion was evaluated by a cross-cut test before ultraviolet irradiation, peeling of the adhesive layer was observed very frequently. [Explanation of symbols]

[0185] 1...Base film 2. Middle class 3...Active energy ray curable adhesive layer 10...Adhesive tape for workpiece processing 11…Dicing tape 12…Removal tape 20…Ring frame 30…Glass substrate 30a...Glass chip (individualized glass substrate) 40…Dicing blade 50...Semiconductor wafer 50'...Thinned semiconductor wafer 51...Circuit 60...Grinder (grinding wheel)

Claims

1. A pressure-sensitive adhesive tape for work processing, comprising a base film made of a polyester resin composition, an intermediate layer, and an active energy ray-curable pressure-sensitive adhesive layer in this order, the intermediate layer is made of a resin composition containing a ternary or higher (meth)acrylic acid ester copolymer (A1) containing methyl acrylate and methacrylic acid as copolymer monomer components, the ternary or higher (meth)acrylic acid ester copolymer (A1) is contained in the resin composition at 90 mass% or more, When the total amount of copolymer monomer components constituting the ternary or higher (meth)acrylic acid ester copolymer (A1) is taken as 100 parts by mass as the standard, The methyl acrylate is contained in an amount of 47 parts by mass or more and 67 parts by mass or less, The methacrylic acid is contained in a range of 2 parts by mass to 7 parts by mass, As a component other than the methyl acrylate and the methacrylic acid, at least one selected from the group consisting of a (meth)acrylic acid ester monomer having a linear or branched alkyl group having from 2 to 20 carbon atoms, a (meth)acrylic acid cycloalkyl ester monomer, a functional group-containing monomer, vinyl acetate, styrene, acrylonitrile, and N-methylvinylpyrrolidone is included in an amount of from 26 to 51 parts by mass, the active energy ray-curable pressure-sensitive adhesive layer is made of a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester copolymer (A2) having a photosensitive carbon-carbon double bond introduced into a side chain of a (meth)acrylic acid ester copolymer base polymer, and a crosslinking agent; The (meth)acrylic acid ester copolymer base polymer contains n-butyl acrylate as a copolymer monomer component in an amount of more than 50 parts by mass and not more than 90 parts by mass, based on 100 parts by mass of the total amount of copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer.

2. The adhesive tape for workpiece processing described in claim 1, wherein the component other than the methyl acrylate and the methacrylic acid is at least one selected from the group consisting of (meth)acrylic acid ester monomers and functional group-containing monomers having a linear or branched alkyl group having a carbon number of 2 or more and 20 or less.

3. The adhesive tape for workpiece processing described in claim 1 or 2, wherein the component other than the methyl acrylate and the methacrylic acid is at least one selected from the group consisting of ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, acrylic acid and 2-hydroxyethyl (meth)acrylate.

4. The adhesive tape for workpiece processing according to any one of claims 1 to 3, wherein the ternary or higher (meth)acrylic acid ester copolymer (A1) is a ternary or higher (meth)acrylic acid ester copolymer containing 2-ethylhexyl acrylate as a copolymer monomer component other than the methyl acrylate and methacrylic acid.

5. The ternary or higher (meth)acrylic acid ester copolymer (A1) is a ternary (meth)acrylic acid ester copolymer having 2-ethylhexyl acrylate, methyl acrylate, and methacrylic acid as copolymerization monomer components, and when the total amount of the copolymer monomer components constituting the ternary (meth)acrylic acid ester copolymer (A1) is taken as 100 parts by mass as a reference, the 2-ethylhexyl acrylate is in the range of 26 parts by mass to 51 parts by mass, the methyl acrylate is in the range of 47 parts by mass to 67 parts by mass, and the methacrylic acid is in the range of 2 parts by mass to 7 parts by mass, and the total amount of the copolymer monomer components is adjusted to 100 parts by mass.

6. The adhesive tape for work processing according to any one of claims 1 to 5, wherein the ternary or higher (meth)acrylic acid ester copolymer (A1) has a glass transition temperature in the range of -36°C or higher and -9°C or lower.

7. The (meth)acrylic acid ester copolymer base polymer is a ternary (meth)acrylic acid ester copolymer having n-butyl acrylate, 2-hydroxyethyl acrylate, and methacrylic acid as copolymer monomer components, and when the total amount of the copolymer monomer components constituting the (meth)acrylic acid ester copolymer base polymer is taken as 100 parts by mass as a reference, the n-butyl acrylate is in the range of 66 parts by mass to 90 parts by mass, the 2-hydroxyethyl acrylate is in the range of 9.8 parts by mass to 31 parts by mass, and the methacrylic acid is in the range of 0.2 parts by mass to 3 parts by mass, and the total amount of the copolymer monomer components is adjusted to 100 parts by mass. The adhesive tape for workpiece processing according to any one of claims 1 to 6.

8. 8. The adhesive tape for workpiece processing according to claim 1, wherein the (meth)acrylic acid ester copolymer base polymer has a glass transition temperature in the range of -50°C or higher and -39°C or lower.

9. The adhesive tape for workpiece processing according to claim 1 , wherein the intermediate layer has a thickness of 5 μm or more.

10. The adhesive tape for workpiece processing according to claim 1 , wherein the active energy ray-curable adhesive layer has a thickness of 5 μm or more.

11. The adhesive tape for workpiece processing according to claim 1 , wherein a sum of a thickness of the intermediate layer and a thickness of the active energy ray-curable adhesive layer is 10 μm or more.

12. 12. The pressure-sensitive adhesive tape for work processing according to claim 1, wherein the base film made of the polyester resin composition is a polyethylene terephthalate film.

13. The adhesive tape for workpiece processing according to any one of claims 1 to 12, wherein the adhesive strength (initial adhesive strength) of the adhesive tape for workpiece processing to a glass plate before irradiation with ultraviolet rays is in the range of 5.0 N / 25 mm or more and 25.0 N / 25 mm or less, and the adhesive strength after irradiation with ultraviolet rays is in the range of 0.01 N / 25 mm or more and 0.50 N / 25 mm or less.

14. The adhesive tape for workpiece processing according to any one of claims 1 to 13, wherein the adhesive strength (initial adhesive strength) of the adhesive tape for workpiece processing to a stainless steel plate (SUS304BA plate) before exposure to ultraviolet rays is in the range of 5.0 N / 25 mm or more and 25.0 N / 25 mm or less, and the adhesive strength after exposure to ultraviolet rays is in the range of 0.01 N / 25 mm or more and 1.0 N / 25 mm or less.

Citation Information

Patent Citations

  • Adhesive sheet for glass substrate dicing and method for dicing glass substrate

    JP2004010829A

  • Adhesive sheet for processing use

    JP2008050406A

  • Dicing tape and method of manufacturing semiconductor chip

    JP2010232301A

  • Adhesive sheet

    JP2013023665A

  • Expandable film, and method for producing semiconductor device by using the film

    JP2014200949A